Polypropylene composition for automotive applications
By blending a specific proportion of heterophase propylene copolymer and vinyl plastics, and using a multi-stage polymerization process and Ziegler-Natta catalyst, the problem of low melt flow rate of existing automotive compositions is solved, achieving high Fluidity and high toughness, suitable for automotive exterior parts.
Patent Information
- Application Number
- CN202380027837.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-23
- Filing Date
- 2023-03-21
- Publication Date
- 2025-01-10
AI Technical Summary
The melt flow rate of the heterophase propylene copolymers of existing automotive compositions is low, which cannot meet the automotive industry's demand for high flowability and high toughness and dimensional stability after processing.
The performance of the composition is adjusted by blending a specific proportion of first and second heterophase propylene copolymer, vinyl plastic and inorganic fillers to obtain a high melt flow rate and a low initial linear thermal expansion coefficient, combined with a multi-stage polymerization process and Ziegler-Natta catalyst system prepares a composition with excellent performance balance.
The excellent performance of the composition in high flow, impact and mechanical properties is achieved, and is suitable for automotive applications, especially in painted and unpainted automotive exterior components.
Smart Images

Figure GDA0005139950500000311 
Figure GDA0005139950500000331 
Figure GDA0005139950500000341
Abstract
Description
Technical Field
[0001] The present invention relates to a composition particularly suitable for automotive applications comprising two heterophasic propylene copolymers having different melt flow rates, an ethylene-based plastomer and an inorganic filler. Background Art
[0002] Compositions suitable for use in the automotive industry typically comprise one or more heterophasic polypropylene copolymers and / or random heterophasic copolymers and usually some inorganic filler.
[0003] There are two trends in the automotive industry:
[0004] - Weight reduction, which requires thin-wall construction and the need to keep mineral reinforcements low.
[0005] - Use of post-industrial or even post-consumer recyclate materials with lower MFR and limited impact strength, which need to be reinforced by other components in the final composition.
[0006] To meet these requirements, compositions suitable for automotive applications need to have high flowability (expressed as a high melt flow rate) and high toughness after processing (expressed as a low initial linear thermal expansion coefficient (CLTE)), and high dimensional stability after processing (expressed as a low shrinkage) is essential.
[0007] The properties of the composition may be adjusted by introducing polymer components (e.g. elastomeric polymers such as plastomers) which adjust the properties of the elastomeric phase of the one or more heterophasic polypropylene copolymers and / or by introducing polymer components (e.g. propylene homopolymers or random copolymers) which adjust the properties of the matrix phase of the one or more heterophasic polypropylene copolymers.
[0008] However, more pronounced effects can be obtained by adjusting the properties of the heterophasic polypropylene copolymer(s) as the main component of the composition.
[0009] WO 2017 / 148970 A1 discloses heterophasic propylene copolymers suitable for automotive compositions. However, these heterophasic propylene copolymers exhibit a rather low melt flow rate MFR of 15 to 70 g / 10 min. 2 , rather low CTLE and low flexural modulus and are therefore not suitable base resins for automotive compositions that will meet the future requirements of the automotive industry.
[0010] Therefore, there is a need in the art for new heterophasic propylene copolymers suitable as a major component in compositions suitable for automotive compositions. It has been found that by carefully tailoring the properties of the heterophasic propylene copolymer used as the major component, in particular the properties of the elastomeric phase, compositions can be obtained showing an excellent balance of properties in terms of high flowability, as manifested by a high melt flow rate, high toughness after processing, as manifested by a low initial coefficient of linear thermal expansion (CLTE), and high dimensional stability after processing, as manifested by low shrinkage. These compositions also show good mechanical properties, impact properties and surface properties, such as low tiger stripes in the MSE surface quality and good paint adhesion, so they are suitable for unpainted and painted automotive applications, such as bumpers. Summary of the invention
[0011] The present invention relates to a composition suitable for automotive applications
[0012] The composition can be obtained by blending at least components (A), (B), (C) and (D)
[0013] (A) 30 to 50 wt.-%, preferably 33 to 48 wt.-%, more preferably 35 to 45 wt.-% of the first heterophasic propylene copolymer;
[0014] (B) 10 to 25 wt.-%, preferably 12 to 22 wt.-%, more preferably 14 to 20 wt.-% of a second heterophasic propylene copolymer;
[0015] (C) 5 to 15 wt %, preferably 10 to 14 wt %, more preferably 10 to 13 wt % of ethylene-based plastomer and
[0016] (D) 5 to 20 wt %, preferably 7 to 18 wt %, more preferably 8 to 17 wt % of an inorganic filler; wherein all percentages are with reference to the total composition, and wherein
[0017] The first heterophasic propylene copolymer (A) comprises a matrix phase and an elastomeric phase dispersed therein and has
[0018] - a melt flow rate MFR of 60 to 250 g / 10 min, preferably 63 to 200 g / 10 min, more preferably 65 to 180 g / 10 min 2 (230°C, 2.16kg, ISO 1133);
[0019] - a soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of 15.0 to 30.0 wt.-%, preferably 17.5 to 27.5 wt.-%, more preferably 20.0 to 25.0 wt.-%;
[0020] - in the range of 40.0 wt % to 75.0 wt %, preferably 42.5 wt % to 70.0 wt %, more preferably 44.0 wt % to 65.0 wt % by quantitative 13 the ethylene content C2(SF) of the soluble fraction determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy; and
[0021] - an intrinsic viscosity iV(SF) of the soluble fraction measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 2.0 to 4.5 dl / g, preferably 2.3 to 4.0 dl / g, more preferably 2.5 to 3.5 dl / g;
[0022] The second heterophasic propylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein and has
[0023] - a melt flow rate MFR of 3.0 to 30 g / 10 min, preferably 4.0 to 25 g / 10 min, more preferably 5.0 to 20 g / 10 min 2 (230°C, 2.16kg, ISO 1133);
[0024] - a xylene cold soluble (XCS) fraction in the range of more than 18.0 to 45.0 wt.-%, preferably 20.0 to 40.0 wt.-%; and
[0025] - an intrinsic viscosity iV(XCS) of the XCS fraction measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 2.5 to 8.5 dl / g, preferably 3.0 to 8.0 dl / g, more preferably 3.5 to 7.5 dl / g;
[0026] The vinyl plastomer (C) is a copolymer of ethylene and a comonomer unit, wherein the comonomer unit is selected from α-olefins having 3 to 12 carbon atoms, preferably from α-olefins having 4 to 10 carbon atoms, most preferably from 1-butene or 1-octene, and the vinyl plastomer (C) has
[0027] - a melt flow rate MFR of 0.5 to 25.0 g / 10 min, preferably 0.8 to 20.0 g / 10 min 2 (190°C, 2.16kg, ISO 1133); and
[0028] -865 to 900 kg / m 3 , preferably 870 to 890 kg / m 3 density; and
[0029] The composition has
[0030] - a melt flow rate MFR of 15 to 80 g / 10 min, preferably 18 to 70 g / 10 min, more preferably 20 to 60 g / 10 min 2 (230°C, 2.16kg, ISO 1133).
[0031] Further, the present invention relates to an article, preferably an injection molded article, more preferably an injection molded automotive article, comprising the composition as described above or below.
[0032] Furthermore, the present invention relates to the use of a composition as described above or below for injection moulding of an article, preferably an automotive article.
[0033] definition
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the invention belongs. Although any method and material similar or equivalent to that described herein can be used to test the present invention in practice, preferred materials and methods are described herein. When describing and advocating the present invention, the following terms will be used according to the definitions described below. Unless otherwise clearly stated, the use of the terms "a", "an", etc. refers to one or more.
[0035] Polymer blends are mixtures of two or more polymer components. Generally, blends can be prepared by mixing two or more polymer components. Suitable mixing procedures known in the art are post-polymerization blending. Post-polymerization blending can be dry blending of polymer components (e.g., polymer powders and / or composite polymer pellets) or melt blending of melt-mixed polymer components.
[0036] A propylene homopolymer is a polymer consisting essentially of propylene monomer units. Due to impurities (especially in commercial polymerization processes), a propylene homopolymer may contain up to 0.20 mol % of comonomer units, preferably up to 0.10 mol % of comonomer units, most preferably up to 0.05 mol % of comonomer units.
[0037] Polypropylene refers to a polymer consisting of units derived from propylene in an amount of more than 50 mol%.
[0038] Polyethylene refers to a polymer consisting of units derived from ethylene in an amount exceeding 50 mol%.
[0039] The term "elastomer" refers to a natural or synthetic polymer that has elasticity. The term "plastomer" refers to a natural or synthetic polymer that combines the properties of elastomers and plastics (e.g., rubber-like properties) and the processing capabilities of plastics. Vinyl plastomers are plastomers composed of units derived from ethylene in an amount exceeding 50 mol%.
[0040] The presence of a multiphase nature can be readily determined by the number of glass transition points, for example in dynamic mechanical analysis (DMA) and / or high resolution microscopy, such as scanning electron microscopy (SEM), transmission electron microscopy (TEM) or atomic force microscopy (AFM).
[0041] The term "XCS" refers to the xylene cold soluble fraction (XCS wt. %) measured at 25°C according to ISO 16152. The term "XCI" refers to the xylene cold insoluble fraction (XCI wt. %) measured at 25°C according to ISO 16152.
[0042] Reactor blends are blends produced from two or more reactors connected in series or from a reactor having two or more reaction chambers. Alternatively, reactor blends can be blended from solutions. Reactor blends are contrasted with compounds produced by melt extrusion.
[0043] The term "recycled" polymer is used to refer to materials recovered from post-consumer waste and / or industrial waste. That is, post-consumer waste refers to articles that have completed at least a first use cycle (or life cycle), i.e., have reached their first use, while industrial waste refers to manufacturing waste that does not normally reach the consumer.
[0044] Accordingly, the term "virgin" refers to newly produced materials and / or articles prior to first use and not being recycled. In the absence of explicit reference to the source of a polymer, the polymer is a "virgin" polymer.
[0045] If not otherwise specified, "%" means weight percent (wt %). DETAILED DESCRIPTION
[0046] Composition
[0047] In a first aspect, the present invention relates to a composition suitable for automotive applications
[0048] The composition can be obtained by blending at least components (A), (B), (C) and (D)
[0049] (A) 30 to 50 wt.-%, preferably 33 to 48 wt.-%, more preferably 35 to 45 wt.-% of the first heterophasic propylene copolymer;
[0050] (B) 10 to 25 wt.-%, preferably 12 to 22 wt.-%, more preferably 14 to 20 wt.-% of a second heterophasic propylene copolymer;
[0051] (C) 5 to 15 wt %, preferably 10 to 14 wt %, more preferably 10 to 13 wt % of ethylene-based plastomer and
[0052] (D) 5 to 20 wt %, preferably 7 to 18 wt %, more preferably 8 to 17 wt % of an inorganic filler; wherein all percentages are with reference to the total composition, and wherein
[0053] The first heterophasic propylene copolymer (A) comprises a matrix phase and an elastomeric phase dispersed therein and has
[0054] - a melt flow rate MFR of 60 to 250 g / 10 min, preferably 63 to 200 g / 10 min, more preferably 65 to 180 g / 10 min 2 (230°C, 2.16kg, ISO 1133);
[0055] - a soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of 15.0 to 30.0 wt.-%, preferably 17.5 to 27.5 wt.-%, more preferably 20.0 to 25.0 wt.-%;
[0056] - in the range of 40.0 wt % to 75.0 wt %, preferably 42.5 wt % to 70.0 wt %, more preferably 44.0 wt % to 65.0 wt % by quantitative 13 the ethylene content C2(SF) of the soluble fraction determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy; and
[0057] - an intrinsic viscosity iV(SF) of the soluble fraction measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 2.0 to 4.5 dl / g, preferably 2.3 to 4.0 dl / g, more preferably 2.5 to 3.5 dl / g;
[0058] The second heterophasic propylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein and has
[0059] - a melt flow rate MFR of 3.0 to 30 g / 10 min, preferably 4.0 to 25 g / 10 min, more preferably 5.0 to 20 g / 10 min 2 (230°C, 2.16kg, ISO 1133);
[0060] - a xylene cold soluble (XCS) fraction in the range of more than 18.0 to 45.0 wt.-%, preferably 20.0 to 40.0 wt.-%; and
[0061] - an intrinsic viscosity iV(XCS) of the XCS fraction measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 2.5 to 8.5 dl / g, preferably 3.0 to 8.0 dl / g, more preferably 3.5 to 7.5 dl / g;
[0062] The vinyl plastomer (C) is a copolymer of ethylene and a comonomer unit, wherein the comonomer unit is selected from α-olefins having 3 to 12 carbon atoms, preferably from α-olefins having 4 to 10 carbon atoms, most preferably from 1-butene or 1-octene, and the vinyl plastomer (C) has
[0063] - a melt flow rate MFR of 0.5 to 25.0 g / 10 min, preferably 0.8 to 20.0 g / 10 min 2 (190°C, 2.16kg, ISO 1133); and
[0064] -865 to 900 kg / m 3 , preferably 870 to 890 kg / m 3 density; and
[0065] The composition has
[0066] - a melt flow rate MFR of 15 to 80 g / 10 min, preferably 18 to 70 g / 10 min, more preferably 20 to 60 g / 10 min 2 (230°C, 2.16kg, ISO 1133).
[0067] The composition according to the invention suitable for automotive applications is particularly suitable for injection molding of articles for vehicle exteriors.
[0068] Compositions suitable for automotive applications according to the present invention have one or more of the following characteristics:
[0069] The composition has a melt flow rate MFR of 15 to 80 g / 10 min, preferably 18 to 70 g / 10 min, more preferably 20 to 60 g / 10 min. 2 (230°C, 2.16kg, ISO 1133).
[0070] The composition can be characterized by CRYSTEX QC analysis. In the CRYSTEX QC analysis, a crystalline fraction (CF) and a soluble fraction (SF) are obtained which can be quantified and analyzed with respect to monomer and comonomer content and intrinsic viscosity (iV).
[0071] The composition preferably exhibits one or all of the following properties in the CRYSTEX QC analysis:
[0072] - a crystalline fraction (CF) content determined according to CRYSTEX QC analysis in the range of 55.0 to 80.0 wt.-%, more preferably 60.0 to 77.0 wt.-%, still more preferably 65.0 to 75.0 wt.-%, and
[0073] - a soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of 20.0 to 45.0 wt.-%, more preferably 23.0 to 40.0 wt.-%, still more preferably 25.0 to 35.0 wt.-%.
[0074] The crystalline fraction (CF) preferably has one or more of the following properties, preferably all of the following properties:
[0075] -4.5 to 12.0 wt %, more preferably 4.8 to 10.0 wt %, still more preferably 5.0 to 9.0 wt % by quantitative 13 Ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy; and / or
[0076] - an intrinsic viscosity (iV(CF)) measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 0.9 to 3.0 dl / g, more preferably 1.0 to 2.8 dl / g, still more preferably 1.1 to 2.5 dl / g.
[0077] The soluble fraction (SF) preferably has one or more of the following properties, preferably all of the following properties:
[0078] -55.0 to 70.0 wt. %, more preferably 57.0 to 67.5 wt. %, still more preferably 58.0 to 65.0 wt. % by quantitative 13 Ethylene content (C2(SF)) determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy; and / or
[0079] - an intrinsic viscosity (iV(SF)) measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 1.8 to 4.0 dl / g, more preferably 2.0 to 3.5 dl / g, still more preferably 2.3 to 3.3 dl / g.
[0080] The composition preferably comprises an amount of 18.0 to 32.0 wt. %, more preferably 19.0 to 30.0 wt. %, still more preferably 20.0 to 28.0 wt. % as determined by the quantitative 13 The units derived from ethylene were determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy.
[0081] The composition according to the invention preferably exhibits an excellent balance of properties with respect to flow properties (as can be seen from the above mentioned melt flow rates), impact properties and in particular mechanical properties (eg with respect to tensile properties).
[0082] The composition preferably has a tensile modulus of from 1750 MPa to 2500 MPa, more preferably from 1800 MPa to 2300 MPa.
[0083] Furthermore, the composition preferably has a tensile elongation at yield of 2.0 to 5.0%, more preferably 3.0 to 4.0%.
[0084] Furthermore, the composition preferably has a tensile elongation at break of 6.5 to 20.0%, more preferably 8.0 to 15.0%.
[0085] Furthermore, the composition has a thermal conductivity of 6.0 kJ / m 2 Up to 20.0kJ / m 2 , more preferably 6.5 kJ / m 2 Up to 15.0kJ / m 2 The charpy notched impact strength at 23°C (CNIS at 23°C) is 2.
[0086] Furthermore, the composition has a thermal conductivity of 3.5 kJ / m 2 Up to 10.0 kJ / m 2 , preferably 3.8 kJ / m 2 Up to 8.5 kJ / m 2 The charpy notched impact strength at -20°C (CNIS at -20°C).
[0087] Still more preferably, the composition has good impact strength in an instrumented puncture test:
[0088] The composition preferably has a puncture energy measured at 23°C of 25.0 to 55.0 J, more preferably 28.0 to 50.0 J.
[0089] The composition preferably has an energy at maximum force measured at 23°C of from 15.0 to 45.0 J, more preferably from 18.0 to 35.0 J.
[0090] Further, the composition preferably has a puncture energy measured at -20°C of 6.6 to 18.0 J, more preferably 6.8 to 15.0 J.
[0091] The composition preferably has an energy at maximum force measured at -20°C of 6.0 to 17.0 J, more preferably 6.5 to 14.0 J.
[0092] Furthermore, the composition preferably has a puncture energy measured at -30°C of 3.0 to 12.0 J, more preferably 3.3 to 10.0 J.
[0093] The composition preferably has an energy at maximum force measured at -30°C of 3.0 to 12.0 J, more preferably 3.3 to 10.0 J.
[0094] The composition of the invention must comprise components (A), (B), (C) and (D) as described above or below in the amounts described accordingly.
[0095] The composition may optionally comprise an additional polymer component, such that the composition is obtainable by blending components (A), (B), (C) and (D) with component (E):
[0096] (E) 5 to 16 wt.%, preferably 7 to 15 wt.%, more preferably 8 to 14 wt.% of a propylene homopolymer;
[0097] wherein all percentages refer to the total composition, and wherein
[0098] The propylene homopolymer (E) has
[0099] - a melt flow rate MFR of 300 to 1500 g / 10 min, preferably 400 to 1300 g / 10 min, more preferably 500 to 1200 g / 10 min 2 (230°C, 2.16kg, ISO 1133).
[0100] The composition preferably further comprises an additive in an amount up to 3.0 wt. %, more preferably in an amount of 0.1 to 3.0 wt. %, still more preferably in an amount of 0.5 to 2.5 wt. %, based on the total weight of the composition.
[0101] Typically, the additives are selected from antioxidants, anti-slip agents, nucleating agents, anti-scratch agents, anti-scorch agents, metal deactivators, UV stabilizers, acid scavengers, lubricants, antistatic agents, pigments, etc., and combinations thereof. These additives are well known in the polymer industry and their use is familiar to those skilled in the art. Any additive present can be added as a separate raw material or in a mixture with a carrier polymer (i.e., a so-called masterbatch).
[0102] It is preferred that all polymer components of the composition are pristine polymers.
[0103] First heterophasic propylene copolymer (A)
[0104] The first heterophasic propylene copolymer (A) comprises a matrix phase and an elastomeric phase dispersed therein.
[0105] The first heterophasic propylene copolymer (A) is characterized in that
[0106] - a melt flow rate MFR of 60 to 250 g / 10 min, preferably 63 to 200 g / 10 min, more preferably 65 to 180 g / 10 min 2 (230°C, 2.16kg, ISO 1133);
[0107] - a soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of 15.0 to 30.0 wt.-%, preferably 17.5 to 27.5 wt.-%, more preferably 20.0 to 25.0 wt.-%;
[0108] -40.0 wt % to 75.0 wt %, preferably 42.5 wt % to 70.0 wt %, more preferably 44.0 wt % to 65.0 wt % by quantitative 13 the ethylene content C2(SF) in the soluble fraction determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy; and
[0109] - an intrinsic viscosity iV(SF) of the soluble fraction measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 2.0 to 4.5 dl / g, preferably 2.3 to 4.0 dl / g, more preferably 2.5 to 3.5 dl / g.
[0110] Preferably, the first heterophasic propylene copolymer (A) has one or more, preferably all, of the following properties:
[0111] - a crystalline fraction (CF) content determined according to CRYSTEX QC analysis in the range of 70.0 to 85.0 wt.-%, more preferably 72.5 to 82.5 wt.-%, more preferably 75.0 to 80.0 wt.-%; and / or
[0112] -3.0 to 20.0 wt%, preferably 3.5 to 15.0 wt%, more preferably 4.0 to 12.0 wt% by quantitative 13 the ethylene content C2(CF) in the crystalline fraction determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy; and / or
[0113] - an intrinsic viscosity iV(CF) of the crystalline fraction measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 0.7 to 1.7 dl / g, preferably 0.8 to 1.5 dl / g, more preferably 0.9 to 1.4 dl / g; and / or
[0114] - a total content of units derived from ethylene (C2) of from 10.0 to 30.0% by weight, preferably from 11.0 to 25.0% by weight, more preferably from 12.5 to 22.5% by weight.
[0115] The ratio of the intrinsic viscosity of the soluble fraction to the crystalline fraction (iV(SF) / iV(CF)) is preferably in the range of 2.2 to 3.0, more preferably in the range of 2.4 to 2.9, still more preferably in the range of 2.6 to 2.8.
[0116] The ratio of the ethylene content of the soluble fraction to the crystalline fraction (C2(SF) / C2(CF)) is preferably in the range of 3.0 to 12.0, more preferably in the range of 4.0 to 11.0, still more preferably in the range of 5.0 to 10.0.
[0117] The first heterophasic propylene copolymer (A) further preferably has one or more, preferably all, of the following properties:
[0118] - a melting temperature Tm of 155 to 175°C, preferably 157 to 172°C, more preferably 160 to 170°C; and / or
[0119] - a crystallization temperature Tc of 120 to 140°C, preferably 122 to 137°C, more preferably 125 to 135°C.
[0120] The first heterophasic propylene copolymer (A) preferably shows a good balance of properties in terms of mechanical properties, impact properties and thermal stability:
[0121] The first heterophasic propylene copolymer (A) preferably has a tensile modulus of 1200 to 1750 MPa, more preferably of 1250 to 1650 MPa, still more preferably of 1300 to 1500 MPa.
[0122] Further, the first heterophasic propylene copolymer (A) preferably has
[0123] -1.0 to 5.0 kJ / m 2 , more preferably 1.3 to 3.5 kJ / m 2 Charpy notched impact strength at 23°C (CNIS at 23°C); and / or
[0124] -1.0 to 6.0 kJ / m 2 , more preferably 1.3 to 5.0 kJ / m 2 The charpy notched impact strength at -20°C (CNIS at -20°C).
[0125] Furthermore, the first heterophasic propylene copolymer (A) preferably has
[0126] - a puncture energy in the instrumented puncture test at 23°C (IPT 23°C) of 0.5 to 5.0 J, more preferably of 0.7 to 3.5 J; and / or
[0127] - Puncture energy in the instrumented penetration test at -20°C (IPT-20°C) of -0.5 to 5.0 J, more preferably of 1.0 to 3.5 J.
[0128] Further, the first heterophasic propylene copolymer (A) preferably has
[0129] - a coefficient of linear thermal expansion in the longitudinal direction (CLTE 23-80°C, MD) in a temperature range of 23 to +80°C at a heating rate of 1°C / min of -115 to 150 μm / m°C, preferably 120 to 140 μm / m°C; and / or
[0130] A coefficient of linear thermal expansion in the transverse direction (CLTE 23-80°C, TD) in the temperature range from 23 to +80°C at a heating rate of 1°C / min of -130 to 160 μm / m°C, preferably 135 to 150 μm / m°C; and / or
[0131] A coefficient of linear thermal expansion in the longitudinal direction (CLTE-30-80°C, MD) in the temperature range of -30 to +80°C at a heating rate of 1°C / min of -105 to 140 μm / m°C, preferably 110 to 130 μm / m°C; and / or
[0132] Coefficient of linear thermal expansion in the transverse direction (CLTE-30-80°C, TD) in the temperature range of -30 to +80°C at a heating rate of 1°C / min of -120 to 155 μm / m°C, preferably 125 to 145 μm / m°C.
[0133] Furthermore, the first heterophasic propylene copolymer (A) preferably has a heat distortion temperature HDTB of 80 to 105 °C, preferably of 85 to 100 °C.
[0134] It is preferred that the first heterophasic propylene copolymer (A) consists of propylene units and ethylene units only.
[0135] Although not measured, the content of units derived from propylene (C3) in the soluble fraction (SF) preferably adds the content of units derived from ethylene (C2) in the soluble fraction (SF) to 100% by weight.
[0136] The content of units derived from propylene (C3) in the soluble fraction (SF) is preferably 25.0 to 60.0 wt%, more preferably 30.0 to 57.5 wt%, still more preferably 35.0 to 56.0 wt%.
[0137] Although not measured, the content of the units (C3) derived from propylene in the crystalline fraction (CF) preferably adds up to 100% by weight with the content of the units (C2) derived from ethylene in the crystalline fraction (CF).
[0138] The content of units derived from propylene (C3) in the crystalline fraction (CF) is preferably 70.0 to 90.0 wt%, more preferably 75.0 to 89.0 wt%, still more preferably 77.5 to 87.5 wt%.
[0139] The total content of propylene derived units (C3) in the first heterophasic polypropylene copolymer (A) is preferably 85.0 to 95.0 wt.-%, more preferably 88.0 to 94.0 wt.-%, still more preferably 90.0 to 93.0 wt.-%.
[0140] The first heterophasic propylene copolymer (A) is preferably a virgin polymer.
[0141] The first heterophasic propylene copolymer (A) may be produced in a multistage process comprising at least two reactors connected in series, wherein in at least one first polymerization step a propylene homopolymer is produced and in at least one subsequent polymerization step the propylene homopolymer is mixed with a propylene ethylene copolymer in the presence of or after the polymerization of said propylene homopolymer to produce the propylene ethylene copolymer.
[0142] However, more ideally the first heterophasic propylene copolymer (A) is produced in a multistage process.
[0143] In an especially preferred embodiment at least the propylene homopolymer matrix is produced in a slurry phase reactor and subsequently at least the propylene copolymer is produced in a gas phase reactor.
[0144] Thus, the first heterophasic propylene copolymer (A) may typically be produced in a cascade of at least 2 reactors, preferably at least 3 reactors, more preferably at least 4 reactors, wherein the first reactor is a liquid bulk reactor, preferably of loop design, and all subsequent reactors are gas phase reactors, preferably of fluidized bed design. The number of subsequent reactors is typically not more than 6, preferably not more than 5. Preferably, the first heterophasic propylene copolymer (A) is produced in a cascade of 4 reactors.
[0145] The preferred multi-stage process is the "loop-gas phase" process developed by Borealis (called Technology) and is described, for example, in the patent literature, for example in EP 0 887 379, WO 92 / 12182, WO 2004 / 000899, WO 2004 / 111095, WO 99 / 24478, WO 99 / 24479 or WO 00 / 68315.
[0146] Another suitable slurry-gas phase process is Basell's Craftsmanship.
[0147] Preferably, the components produced in the first two reactors are crystallizable propylene homopolymers, whereas the components produced in the subsequent third and fourth reactors are predominantly amorphous copolymers having a higher comonomer content.
[0148] It is preferred that the heterophasic propylene copolymer (A) is polymerized in a process comprising the following steps:
[0149] a) polymerizing propylene in a first polymerization reactor in the presence of a specific Ziegler-Natta catalyst system as described below to produce a first propylene homopolymer fraction;
[0150] b) transferring the polymerization mixture comprising the Ziegler-Natta catalyst system and the first propylene homopolymer fraction from the first polymerization reactor to a second polymerization reactor;
[0151] c) polymerizing propylene in the presence of a Ziegler-Natta catalyst system in a second polymerization reactor to produce a second propylene homopolymer fraction;
[0152] d) transferring the polymerization mixture comprising the Ziegler-Natta catalyst system and the first and second propylene homopolymer fractions from the second polymerization reactor to a third polymerization reactor;
[0153] e) polymerizing propylene and ethylene in the presence of a Ziegler-Natta catalyst system in a third polymerization reactor to produce a first propylene-ethylene copolymer fraction;
[0154] f) transferring the polymerization mixture comprising the Ziegler-Natta catalyst system, the first and second propylene homopolymer fractions and the first propylene-ethylene copolymer fraction from the third polymerization reactor to a fourth polymerization reactor;
[0155] g) polymerizing propylene and ethylene in the presence of a Ziegler-Natta catalyst system in a fourth polymerization reactor to produce a second propylene-ethylene copolymer fraction;
[0156] h) withdrawing a polymerization mixture comprising the Ziegler-Natta catalyst system, the first and second propylene homopolymer fractions and the first and second propylene-ethylene copolymer fractions from the fourth polymerization reactor; and
[0157] i) obtaining a polymer powder comprising a first and a second propylene homopolymer fraction and a first and a second propylene-ethylene copolymer fraction.
[0158] The first polymerisation reactor is preferably a slurry phase reactor, such as a loop reactor.
[0159] It is preferred that the operating temperature in the first polymerisation reactor, preferably the loop reactor, is in the range of 62 to 85 °C, more preferably in the range of 65 to 82 °C, still more preferably in the range of 67 to 80 °C.
[0160] Typically, the pressure in the first polymerisation reactor, preferably a loop reactor, is in the range of 20 to 80 bar, preferably 30 to 70 bar, for example 35 to 65 bar.
[0161] It is preferred that a propylene homopolymer is produced in the first polymerization reactor, preferably a loop reactor. Accordingly, it is preferred that the first propylene polymer fraction is a first propylene homopolymer fraction.
[0162] Preferably, hydrogen is added in the first polymerization reactor to control the molecular weight, i.e. the melt flow rate MFR 2 .
[0163] Preferably, the ratio of hydrogen to propylene (H2 / C3 ratio) in the first polymerization reactor, preferably a loop reactor, is in the range of 20 to 50 mol / kmol, more preferably 30 to 40 mol / kmol.
[0164] Due to the high hydrogen content the melt flow rate of the first propylene polymer fraction is very high.
[0165] It is preferred that the first propylene polymer fraction has a melt flow rate MFR in the range of 50 to 1000 g / 10 min, preferably in the range of 150 to 850 g / 10 min, more preferably in the range of 300 to 700 g / 10 min. 2 (230°C, 2.16kg, ISO 1133).
[0166] The second polymerization reactor is preferably a first gas phase reactor, such as a first fluidized bed gas phase reactor.
[0167] It is preferred that the operating temperature in the second polymerisation reactor, preferably the first gas phase reactor, is in the range of 75 to 95 °C, more preferably in the range of 78 to 92 °C.
[0168] Typically, the pressure in the second polymerization reactor, preferably the first gas phase reactor, is in the range of 5 to 50 bar, preferably in the range of 15 to 40 bar.
[0169] It is preferred that a propylene homopolymer is produced in the second polymerization reactor, preferably the first gas phase reactor. Accordingly, it is preferred that the second propylene polymer fraction is a second propylene homopolymer fraction.
[0170] Preferably, hydrogen is added in the second polymerization reactor to control the molecular weight, i.e. the melt flow rate MFR 2 .
[0171] Preferably, the ratio of hydrogen to propylene (H2 / C3 ratio) in the second polymerization reactor (preferably the first gas phase reactor) is in the range of 150 to 500 mol / kmol, more preferably in the range of 200 to 350 mol / kmol.
[0172] Due to the high hydrogen content the melt flow rate of the combined first and second propylene polymer fractions is very high.
[0173] It is preferred that the combined first and second propylene polymer fractions have a melt flow rate MFR in the range of 50 to 1000 g / 10 min, preferably in the range of 150 to 850 g / 10 min, more preferably in the range of 300 to 700 g / 10 min. 2 (230°C, 2.16kg, ISO 1133).
[0174] The third polymerization reactor is preferably a second gas phase reactor, such as a second fluidized bed gas phase reactor.
[0175] It is preferred that the operating temperature in the third polymerization reactor (preferably the second gas phase reactor) is in the range of 65 to 85° C., more preferably in the range of 68 to 82° C. Typically, the operating temperature in the third polymerization reactor is lower than the operating temperature in the second polymerization reactor.
[0176] Typically, the pressure in the third polymerization reactor, preferably the second gas phase reactor, is in the range of 5 to 40 bar, preferably 10 to 30 bar.
[0177] In the third polymerization reactor, preferably the second gas phase reactor, a propylene ethylene copolymer is produced. Thus, the third propylene polymer fraction is the first propylene ethylene copolymer fraction.
[0178] The ratio of ethylene to propylene (C2 / C3 ratio) in the third polymerization reactor (preferably the second gas phase reactor) is in the range of 500 to 2500 mol / kmol, more preferably 700 to 2000 mol / kmol.
[0179] Due to the high ethylene to propylene ratio (C2 / C3 ratio) the third propylene polymer fraction is preferably an elastomeric block copolymer having a propylene-rich portion and an ethylene-rich portion.
[0180] Preferably, hydrogen is added in the third polymerization reactor to control the molecular weight, i.e., the melt flow rate MFR 2 .
[0181] Preferably, the ratio of hydrogen to ethylene (H2 / C2 ratio) in the third polymerization reactor (preferably the second gas phase reactor) is in the range of 50 to 250 mol / kmol, more preferably 100 to 200 mol / kmol.
[0182] It is preferred that the combined first, second and third propylene polymer fractions have a melt flow rate MFR in the range of 75 to 500 g / 10 min, preferably in the range of 80 to 350 g / 10 min, more preferably in the range of 85 to 250 g / 10 min. 2 (230°C, 2.16kg, ISO 1133).
[0183] The fourth polymerization reactor is preferably a third gas phase reactor, such as a third fluidized bed gas phase reactor.
[0184] It is preferred that the operating temperature in the fourth polymerization reactor (preferably the third gas phase reactor) is in the range of 65 to 85° C., more preferably in the range of 68 to 82° C. Typically, the operating temperature in the fourth polymerization reactor is lower than the operating temperature in the second polymerization reactor.
[0185] Typically, the pressure in the fourth polymerization reactor, preferably the third gas phase reactor, is in the range of 5 to 40 bar, preferably 10 to 30 bar.
[0186] In the fourth polymerization reactor (preferably the third gas phase reactor), a propylene ethylene copolymer is produced. Thus, the fourth propylene polymer fraction is the second propylene ethylene copolymer fraction.
[0187] The ratio of ethylene to propylene (C2 / C3 ratio) in the fourth polymerization reactor (preferably the third gas phase reactor) is in the range of 500 to 2500 mol / kmol, more preferably 700 to 2000 mol / kmol.
[0188] Due to the high ethylene to propylene ratio (C2 / C3 ratio), the fourth propylene polymer fraction is preferably an elastomeric block copolymer having a propylene-rich portion and an ethylene-rich portion.
[0189] Preferably, hydrogen is added in the fourth polymerization reactor to control the molecular weight, i.e., the melt flow rate MFR 2 .
[0190] Preferably, the ratio of hydrogen to ethylene (H2 / C2 ratio) in the fourth polymerization reactor (preferably the third gas phase reactor) is in the range of 50 to 250 mol / kmol, more preferably 80 to 175 mol / kmol.
[0191] It is preferred that the combined first, second, third and fourth propylene polymer fractions have a melt flow rate MFR in the range of 50 to 250 g / 10 min, preferably 53 to 200 g / 10 min, more preferably 55 to 180 g / 10 min. 2 (230°C, 2.16kg, ISO 1133).
[0192] Furthermore, the first, second, third and fourth propylene polymer fraction combined preferably has a total comonomer content, preferably ethylene (C2) content, in the range of 10.0 to 30.0 wt.-%, preferably 11.0 to 25.0 wt.-%, more preferably 12.5 to 22.5 wt.-%, based on the total weight of the first, second, third and fourth propylene polymer fraction combined, as determined by quantitative 13 The results were determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy.
[0193] The combined first, second, third and fourth propylene polymer fraction preferably forms a heterophasic propylene copolymer.
[0194] The preparation of the first, second, third and fourth propylene polymer fractions may comprise, in addition to a (main) polymerization stage carried out in at least four polymerization reactors, a preceding prepolymerization carried out in a prepolymerization reactor upstream of the first polymerization reactor.
[0195] In the prepolymerization reactor, polypropylene is produced. The prepolymerization is preferably carried out in the presence of a Ziegler-Natta catalyst system. According to this embodiment, the Ziegler-Natta catalyst system is introduced into the prepolymerization step. However, this should not exclude the option of adding, for example, further cocatalysts during the polymerization process (e.g. in the first reactor) at a later stage. In one embodiment, if prepolymerization is applied, all components of the Ziegler-Natta catalyst system are added only in the prepolymerization reactor.
[0196] The prepolymerization reaction is usually carried out at a temperature of 0 to 60°C, preferably 15 to 50°C, more preferably 20 to 45°C.
[0197] The pressure in the prepolymerisation reactor is not critical but must be high enough to keep the reaction mixture in the liquid phase. Thus, the pressure may be from 20 to 100 bar, for example from 30 to 70 bar.
[0198] In a preferred embodiment the prepolymerization is carried out as bulk slurry polymerization in liquid propylene, ie the liquid phase comprises mainly propylene, optionally with dissolved inert components.
[0199] It is possible that other components are also added to the prepolymerization stage. Thus, hydrogen may be added to the prepolymerization stage to control the molecular weight of the polypropylene, as known in the art. Further, antistatic additives may be used to prevent the particles from sticking to each other or to the walls of the reactor.
[0200] Precise control of prepolymerization conditions and reaction parameters is within the skill of the art.
[0201] Due to the above defined process conditions in the prepolymerization, preferably a mixture of the Ziegler-Natta catalyst system and the polypropylene produced in the prepolymerization reactor is obtained. Preferably, the Ziegler-Natta catalyst system is (finely) dispersed in the polypropylene. In other words, the Ziegler-Natta catalyst system introduced in the prepolymerization reactor is split into smaller fragments, which are evenly distributed in the growing polypropylene. The size of the introduced Ziegler-Natta catalyst system and of the obtained fragments is not critical for the present invention and is within the knowledge of a person skilled in the art.
[0202] As mentioned above, if prepolymerization is used, after the prepolymerization, the mixture of the Ziegler-Natta catalyst system and the polypropylene produced in the prepolymerization reactor is transferred to the first polymerization reactor. Typically, the total amount of the polypropylene produced in the prepolymerization reactor in the first, second and third propylene polymer fractions is quite low and typically does not exceed 5.0 wt%, more preferably does not exceed 4.0 wt%, more preferably in the range of 0.5 to 4.0 wt%, for example in the range of 1.0 to 3.0 wt%.
[0203] In case no prepolymerization is used, propylene and other ingredients (eg, Ziegler-Natta catalyst system) are introduced directly into the first polymerization reactor.
[0204] The residence time of the polymerization mixture in the different polymerization stages is adjusted to obtain the amounts of the first, second, third and fourth polymer fractions in the combined first, second, third and fourth polymer fractions.
[0205] Preferably, the first propylene polymer fraction is present in an amount of 35 to 55 wt %, more preferably 40 to 50 wt %, based on the total weight of the combined first, second, third and fourth propylene polymer fractions. If present, the amount of the polypropylene produced in the prepolymerization reactor is usually added to the amount of the first propylene polymer fraction.
[0206] Preferably, the second propylene polymer fraction is present in an amount of 25 to 45 wt%, more preferably 30 to 40 wt%, based on the total weight of the first, second, third and fourth propylene polymer fractions combined.
[0207] Preferably the third propylene polymer fraction is present in an amount of 5 to 20 wt%, more preferably 10 to 15 wt%, based on the total weight of the first, second, third and fourth propylene polymer fractions combined.
[0208] Preferably the fourth propylene polymer fraction is present in an amount of 3 to 15 wt%, more preferably 5 to 10 wt%, based on the total weight of the first, second, third and fourth propylene polymer fractions combined.
[0209] According to the present invention the first heterophasic propylene copolymer (A) is preferably obtained by a multistage polymerisation process as described above in the presence of a Ziegler-Natta catalyst system.
[0210] As mentioned above in the specific process for the preparation of the first heterophasic propylene copolymer (A) as defined above preferably a specific Ziegler-Natta catalyst is used.
[0211] Accordingly, the Ziegler-Natta catalyst system will now be described in more detail.
[0212] The catalyst used in the present invention is a solid Ziegler-Natta catalyst comprising a compound of an IUPAC Group 4 to 6 transition metal (such as titanium), a Group 2 metal compound (such as magnesium), and an internal donor, which is preferably a non-phthalic acid compound, more preferably a non-phthalic acid ester, still more preferably a non-phthalic acid diester, as described in more detail below. Therefore, the catalyst is completely free of unwanted phthalic acid compounds. Further, the solid catalyst does not contain any external support material, such as silica or MgCl2, but the catalyst is self-supported.
[0213] Ziegler-Natta catalysts (ZN-C) can be further defined by the way in which they are obtained.
[0214] Therefore, the Ziegler-Natta catalyst (ZN-C) is preferably obtained by a process comprising the following steps:
[0215] a)
[0216] a 1 ) providing a solution of at least a Group 2 metal alkoxide (Ax) which is the reaction product of a Group 2 metal compound and a monohydric alcohol (A) which, in addition to the hydroxyl moieties, comprises at least one ether moiety, optionally in an organic liquid reaction medium; or
[0217] a 2 ) providing a solution of at least a Group 2 metal alkoxide (Ax') which is the reaction product of a Group 2 metal compound with a monohydric alcohol (A) and an alcohol mixture of a monohydric alcohol (B) of formula ROH, optionally in an organic liquid reaction medium; or
[0218] a 3 ) providing a solution of a mixture of a Group 2 alkoxide (Ax) and a Group 2 metal alkoxide (Bx) which is the reaction product of a Group 2 metal compound and a monohydric alcohol (B), optionally in an organic liquid reaction medium; or
[0219] a 4 ) provides a formula M(OR 1 ) n (OR 2 ) m X 2-n-m A Group 2 alkoxide or a Group 2 alkoxide M(OR 1 ) n’ X 2-n’ and M(OR 2 ) m’ X 2-m’A solution of a mixture, wherein M is a Group 2 metal, X is a halogen, R 1 and R 2 are different alkyl groups having from C 2 to C 16 carbon atoms, and 0 ≤ n < 2, 0 ≤ m < 2 and n + m+(2 - n - m)=2, provided that neither n nor m is 0, 0 < n' ≤ 2 and 0 < m' ≤ 2; and
[0220] b) adding the solution from step a) to a compound of at least one transition metal of Groups 4 to 6, and
[0221] c) obtaining solid catalyst component particles,
[0222] and adding an internal electron donor, preferably a non-phthalic internal donor, in any step prior to step c).
[0223] The internal donor or its precursor is preferably added to the solution of step a).
[0224] According to the above procedure, the Ziegler - Natta catalyst can be obtained by a precipitation method or an emulsion (liquid / liquid two - phase system) - solidification method, depending on the physical conditions, especially the temperature used in steps b) and c).
[0225] In both methods (precipitation or emulsion - solidification), the chemical properties of the catalyst are the same.
[0226] In the precipitation method, the combination of the solution of step a) with at least one transition metal compound in step b) is carried out, and the entire reaction mixture is maintained at at least 50 °C, more preferably in the temperature range of 55 °C to 110 °C, more preferably in the range of 70 °C to 100 °C, to ensure complete precipitation of the catalyst component in the form of solid particles (step c).
[0227] In the emulsion - solidification method in step b), the solution of step a) is usually added to at least one transition metal compound at a lower temperature, such as - 10 to less than 50 °C, preferably - 5 to 30 °C. During the emulsion stirring, the temperature is usually maintained at - 10 to less than 40 °C, preferably - 5 to 30 °C. The droplets of the emulsion dispersed phase form the active catalyst composition. The solidification of the droplets (step c) is suitably carried out by heating the emulsion to a temperature of 70 to 150 °C, preferably 80 to 110 °C.
[0228] The catalyst prepared by the emulsion - solidification method is preferably used in the present invention.
[0229] In a preferred embodiment, a 2 ) or a 3), that is, a solution of (Ax') or a solution of a mixture of (Ax) and (Bx).
[0230] Preferably, the Group 2 metal is magnesium.
[0231] The alkoxymagnesium compounds (Ax), (Ax') and (Bx) can be prepared in situ in the first step (i.e. step a)) of the catalyst preparation process by reacting a magnesium compound with an alcohol (or alcohols) as described above, or the alkoxymagnesium compounds can be separately prepared alkoxymagnesium compounds, or they can even be purchased as ready-made alkoxymagnesium compounds on the market and used as such in the catalyst preparation process of the present invention.
[0232] Illustrative examples of alcohol (A) are monoethers of diols (glycol monoethers). Preferred alcohols (A) are C 2 To C 4 Glycol monoethers, wherein the ether moiety contains 2 to 18 carbon atoms, preferably 4 to 12 carbon atoms. Preferred examples are 2-(2-ethylhexyloxy)ethanol, 2-butoxyethanol, 2-hexyloxyethanol and 1,3-propylene glycol monobutyl ether, 3-butoxy-2-propanol, of which 2-(2-ethylhexyloxy)ethanol and 1,3-propylene glycol monobutyl ether, 3-butoxy-2-propanol are particularly preferred.
[0233] Exemplary monohydric alcohols (B) have the formula ROH, where R is a linear or branched C 6 -C 10 The most preferred monohydric alcohol is 2-ethyl-1-hexanol or octanol.
[0234] Preference is given to using mixtures of alkoxymagnesium compounds (Ax) and (Bx) or mixtures of alcohols (A) and (B), respectively, in a ratio of Bx:Ax or B:A of 8:1 to 2:1, more preferably 5:1 to 3:1.
[0235] The alkoxymagnesium compound may be the reaction product of an alcohol (or alcohols) as defined above and a magnesium compound selected from dialkylmagnesium, alkylmagnesium alkoxy, dialkoxymagnesium, alkoxymagnesium halide and alkylmagnesium halide. The alkyl groups may be similar or different C 1 -C 20 Alkyl, preferably C 2 -C 10 Alkyl. When used, typical alkyl alkoxy magnesium compounds are ethyl butoxy magnesium, butyl pentoxy magnesium, octyl butoxy magnesium and octyl octoxy magnesium. Preferably, dialkyl magnesium is used. The most preferred dialkyl magnesium is butyl octyl magnesium or butyl ethyl magnesium.
[0236] It is also possible that the magnesium compound, in addition to reacting with alcohol (A) and alcohol (B), can also react with a compound of formula R" (OH) mThe polyol (C) is reacted to obtain the alkoxy magnesium compound. If used, the preferred polyol is an alcohol, wherein R" is a linear, cyclic or branched C 2 To C 10 A hydrocarbon residue, and m is an integer from 2 to 6.
[0237] Thus, the alkoxymagnesium compound in step a) is selected from the group consisting of dialkoxymagnesium, diaryloxymagnesium, alkoxymagnesium halides, aryloxymagnesium halides, alkylalkoxymagnesium, arylalkoxymagnesium and alkylaryloxymagnesium. In addition, mixtures of dihalide and dialkoxymagnesium may be used.
[0238] The solvent for preparing the catalyst can be selected from aromatic and aliphatic straight chain, branched and cyclic hydrocarbons or mixtures thereof having 5 to 20 carbon atoms, more preferably 5 to 12 carbon atoms. Suitable solvents include benzene, toluene, cumene, xylene, pentane, hexane, heptane, octane and nonane. Hexane and pentane are particularly preferred.
[0239] The Mg compound is usually provided as a 10 to 50 wt% solution in the above mentioned solvents. Typical commercially available solutions of Mg compounds, especially dialkylmagnesium, are 20-40 wt% solutions in toluene or heptane.
[0240] The reaction for preparing the alkoxymagnesium compound can be carried out at a temperature of 40° C. to 70° C. The most suitable temperature is selected depending on the Mg compound and the alcohol(s) used.
[0241] The transition metal compound of Groups 4 to 6 is preferably a titanium compound, most preferably a titanium halide such as TiCl 4 .
[0242] The non-phthalic internal donor used for the preparation of the catalyst used in the present invention is preferably selected from non-phthalic (di)carboxylic acid (di)esters, 1,3-diethers, derivatives thereof and mixtures thereof. Particularly preferred donors are diesters of monounsaturated dicarboxylic acids, in particular esters belonging to the group comprising malonates, maleates, succinates, citraconates, glutarates, cyclohexene-1,2-dicarboxylates and benzoates and any derivatives and / or mixtures thereof. Preferred examples are, for example, substituted maleates and citraconates, most preferably citraconates.
[0243] In the emulsion process, a two-phase liquid-liquid system can be formed by simple stirring and optionally adding (additional) solvents and additives such as turbulence minimizing agents (TMA) and / or emulsifiers and / or emulsion stabilizers such as surfactants, which are used in a manner known in the art to promote the formation of the emulsion and / or stabilize the emulsion. Preferably, the surfactant is an acrylic or methacrylic polymer. Particularly preferred are unbranched C 12To C 20 (Meth)acrylates, such as poly(hexadecyl)methacrylate and poly(octadecyl)methacrylate and mixtures thereof. If a turbulence minimizing agent (TMA) is used, it is preferably selected from α-olefin polymers of α-olefin monomers having 6 to 20 carbon atoms, such as polyoctenes, polynonenes, polydecenes, polyundecenes or polydodecenes or mixtures thereof. Most preferably it is polydecene.
[0244] The solid particulate product obtained by precipitation or emulsion-solidification can be washed at least once, preferably at least twice, and most preferably at least three times with aromatic and / or aliphatic hydrocarbons, preferably with toluene, heptane or pentane. The catalyst can be further dried, for example by evaporation or flushing with nitrogen, or it can be slurried into an oily liquid without any drying step.
[0245] The Ziegler-Natta catalyst finally obtained is preferably in the form of particles, the average particle size of which is generally in the range of 5 to 200 μm, preferably 10 to 100 μm. The particles are dense and have low porosity and have a particle size of less than 20 g / m 2 , more preferably less than 10 g / m 2 Typically, the amount of Ti is 1 to 6 wt % of the catalyst composition, the amount of Mg is 10 to 20 wt % of the catalyst composition, and the amount of the donor is 10 to 40 wt % of the catalyst composition.
[0246] Detailed descriptions of catalyst preparation are disclosed in WO 2012 / 007430, EP2610271, EP 261027 and EP2610272, which are incorporated herein by reference.
[0247] Ziegler-Natta catalysts are used together with an alkylaluminum cocatalyst, preferably with an external donor.
[0248] As a further component in the present polymerization process, an external donor is preferably present. Suitable external donors include certain silanes, ethers, esters, amines, ketones, heterocyclic compounds and blends thereof. Particular preference is given to using silanes. Most preferably, silanes of the general formula
[0249] R a p R b q Si(OR c ) (4-p-q)
[0250] Where R a , R b and R c represents a hydrocarbon group, in particular an alkyl or cycloalkyl group, and wherein p and q are numbers from 0 to 3, the sum of which p+q is equal to or less than 3. R a, R b and R c can be selected independently of each other and can be the same or different. Specific examples of such silanes include (tert-butyl) 2 Si(OCH 3 ) 2 、(Cyclohexyl)(methyl)Si(OCH 3 ) 2 、(phenyl) 2 Si(OCH 3 ) 2 and (cyclopentyl) 2 Si(OCH 3 ) 2 , or a silane having the following general formula
[0251] Si(OCH 2 CH 3 ) 3 (NR 3 R 4 )
[0252] Where R 3 and R 4 The may be the same or different and represent a hydrocarbon group having 1 to 12 carbon atoms.
[0253] R 3 and R 4 are independently selected from the group consisting of a linear aliphatic hydrocarbon group having 1 to 12 carbon atoms, a branched aliphatic hydrocarbon group having 1 to 12 carbon atoms, and a cyclic aliphatic hydrocarbon group having 1 to 12 carbon atoms. 3 and R 4 Independently selected from the group consisting of methyl, ethyl, n-propyl, n-butyl, octyl, decyl, isopropyl, isobutyl, isopentyl, tert-butyl, tert-pentyl, neopentyl, cyclopentyl, cyclohexyl, methylcyclopentyl and cycloheptyl.
[0254] More preferably, R 3 and R 4 Same, still more preferably, R 3 and R 4 All are ethyl.
[0255] Particularly preferred external donors are dicyclopentyldimethoxysilane donors (D-donors) or cyclohexylmethyldimethoxysilane donors (C-donors).
[0256] In addition to the Ziegler-Natta catalyst and the optional external donor, a cocatalyst must be used. The cocatalyst is preferably a compound of Group 13 of the Periodic Table of Elements (IUPAC), such as an organoaluminum, such as an aluminum compound, such as an alkylaluminum, an aluminum halide or an alkylaluminum halide compound. Thus, in a particular embodiment, the cocatalyst is a trialkylaluminum, such as triethylaluminum (TEAL), a dialkylaluminum chloride or an alkylaluminum dichloride or a mixture thereof. In a particular embodiment, the cocatalyst is triethylaluminum (TEAL).
[0257] Preferably, the ratio between the cocatalyst (Co) and the external donor (ED) [Co / ED] and / or the ratio between the cocatalyst (Co) and the transition metal (TM) [Co / TM] should be carefully selected.
[0258] therefore,
[0259] (a) the molar ratio of the cocatalyst (Co) to the external donor (ED) [Co / ED] must be in the range of 5 to 45, preferably in the range of 5 to 35, more preferably in the range of 5 to 25; and optionally
[0260] (b) The molar ratio of the co-catalyst (Co) to the titanium compound (TC) [Co / TC] must be in the range of more than 80 to 500, preferably in the range of 100 to 350, still more preferably in the range of 120 to 300.
[0261] The first heterophasic propylene copolymer (A) according to this invention is preferably produced in the presence of:
[0262] (a) a Ziegler-Natta catalyst comprising an IUPAC Group 4 to 6 transition metal compound (TC), a Group 2 metal compound and an internal donor, wherein the internal donor is a non-phthalic acid compound, preferably a non-phthalic acid ester, still more preferably a diester of a non-phthalic dicarboxylic acid;
[0263] (b) optionally a co-catalyst (Co), and
[0264] (c) Optional external donor (ED).
[0265] It is preferred that the internal donor (ID) is selected from optionally substituted malonates, maleates, succinates, glutarates, cyclohexene-1,2-dicarboxylates, benzoates and derivatives and / or mixtures thereof, preferably the internal donor (ID) is a citraconate. Additionally or alternatively, the molar ratio of the cocatalyst (Co) to the external donor (ED) [Co / ED] is from 5 to 45.
[0266] It is preferred that the nucleating agent is introduced into the composition during the polymerization of the first heterophasic propylene copolymer (A). The nucleating agent is preferably introduced into the first heterophasic propylene copolymer (A) by first polymerizing a vinyl compound, preferably a vinyl cycloalkane, in the presence of a Ziegler-Natta catalyst system and then using the resulting reaction mixture of the polymer of the vinyl compound, preferably a vinyl cyclohexane (VCH) polymer and the catalyst system for the production of the first heterophasic propylene copolymer (A). The above introduction of a polymer nucleating agent into the first heterophasic propylene copolymer (A) during the polymerization of the first heterophasic propylene copolymer (A) is herein referred to as BNT technology.
[0267] With regard to the BNT technology, reference is made to the international applications WO 99 / 24478, WO 99 / 24479 and in particular WO 00 / 68315. According to this technology, a catalyst system, preferably a Ziegler-Natta procatalyst, can be modified by polymerizing a vinyl compound in the presence of a catalyst system comprising in particular a special Ziegler-Natta procatalyst, an external donor and a cocatalyst, the vinyl compound having the formula: CH 2 =CH-CHR 1 R 2
[0268] Where R 1 and R 2 Together with the carbon atoms to which they are attached, they form an optionally substituted saturated or unsaturated or aromatic ring or fused ring system, wherein the ring or fused ring portion contains 4 to 20 carbon atoms, preferably a 5 to 12-membered saturated or unsaturated or aromatic ring or fused ring system, or independently represent a straight or branched C 4 -C 30 Alkanes, C 4 -C 20 Cycloalkanes or C 4 -C 20 Preferably, R 1 and R 2 Together with the C atoms to which they are attached, they form a five- or six-membered saturated or unsaturated or aromatic ring, or independently represent a lower alkyl group containing 1 to 4 carbon atoms. Preferred vinyl compounds for preparing the polymer nucleating agents used according to the invention are in particular vinylcycloalkanes, in particular vinylcyclohexane (VCH), vinylcyclopentane and vinyl-2-methylcyclohexane, 3-methyl-1-butene, 3-ethyl-1-hexene, 3-methyl-1-pentene, 4-methyl-1-pentene or mixtures thereof. VCH is a particularly preferred monomer.
[0269] The polymeric vinyl compound is used as an α-nucleating agent. The weight ratio of the vinyl compound to the solid catalyst component in the catalyst modification step is preferably up to 5 (5:1), preferably up to 3 (3:1), most preferably from 0.5 (1:2) to 2 (2:1). The most preferred vinyl compound is vinylcyclohexane (VCH).
[0270] When the nucleating agent is introduced into the first heterophasic propylene copolymer (A) during the polymerization, the amount of nucleating agent present in the first heterophasic propylene copolymer (A) is preferably not more than 500 ppm, more preferably not more than 200 ppm, still more preferably in the range of 1.0 to 200 ppm, most preferably from 5.0 to 100 ppm, based on the total weight of first heterophasic propylene copolymer (A) and nucleating agent, preferably based on the total weight of the first heterophasic propylene copolymer (A) including all additives.
[0271] Second heterophasic propylene copolymer (B)
[0272] The heterophasic polypropylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein.
[0273] The second heterophasic propylene copolymer (B) is characterized in that
[0274] - a melt flow rate MFR of 3.0 to 30 g / 10 min, preferably 4.0 to 25 g / 10 min, more preferably 5.0 to 20 g / 10 min 2 (230°C, 2.16kg, ISO 1133);
[0275] - a xylene cold soluble (XCS) fraction in the range of 18.0 to 45.0 wt.-%, preferably 20.0 to 40.0 wt.-%; and
[0276] - an intrinsic viscosity iV(XCS) of the XCS fraction measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 2.5 to 8.5 dl / g, preferably 3.0 to 8.0 dl / g, more preferably 3.5 to 7.5 dl / g.
[0277] By quantitative 13 The ethylene content (C2) C2(SF) in the soluble fraction, determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy, is preferably from 18.0 to less than 40.0% by weight, preferably from 20.0 to 38.0% by weight, more preferably from 22.0 to 33.0% by weight.
[0278] The second heterophasic propylene copolymer (B) preferably has
[0279] - a xylene cold insoluble (XCI) fraction in the range of 55.0 to 82.0 wt. %, more preferably 60.0 to 80.0 wt. %, and / or
[0280] -0 to 2.5 wt%, more preferably 0.5 to 2.2 wt% by quantitative 13 the ethylene content C2(XCI) in said XCI fraction determined by C-NMR spectroscopy; and / or
[0281] - an intrinsic viscosity iV(CF) of the XCI fraction measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 1.0 to 3.5 dl / g, more preferably of 1.5 to 3.0 dl / g; and / or
[0282] - a total content of units derived from ethylene (C2) of 5.0 to 20.0 wt.-%, preferably more preferably 5.5 to 18.0 wt.-%.
[0283] Preferably, the second heterophasic propylene copolymer (B) has one or more, preferably all, of the following properties:
[0284] - a melting temperature Tm of 155 to 175°C, preferably 157 to 172°C, more preferably 160 to 170°C; and / or
[0285] - Crystallization temperature Tc of 105 to 125°C, preferably 107 to 122°C, more preferably 110 to 120°C.
[0286] It is preferred that the second heterophasic propylene copolymer (B) consists of propylene units and ethylene units.
[0287] Although not measured, the content of the units (C3) derived from propylene in the soluble fraction (SF) preferably adds up to 100% by weight with the content of the units (C2) derived from ethylene in the soluble fraction (SF).
[0288] The content of propylene-derived units (C3) in the soluble fraction (SF) is preferably from more than 60.0 to 82.0 wt.-%, more preferably from 62.0 to 80.0 wt.-%, still more preferably from 67.0 to 78.0 wt.-%.
[0289] Although not measured, the content of the units (C3) derived from propylene in the crystalline fraction (CF) preferably adds up to 100% by weight with the content of the units (C2) derived from ethylene in the crystalline fraction (CF).
[0290] The content of units derived from propylene (C3) in the crystalline fraction (CF) is preferably from 97.5 to 100 wt.-%, more preferably from 97.8 to 99.5 wt.-%.
[0291] The total content of propylene derived units (C3) in the second heterophasic propylene copolymer (B) is preferably from 80.0 to 95.0 wt.-%, more preferably from 82.0 to 94.5 wt.-%.
[0292] The second heterophasic propylene copolymer (B) is preferably a pristine polymer.
[0293] The second heterophasic propylene copolymer (B) is preferably obtained in a multistage polymerization process comparable to the one described for the first heterophasic propylene copolymer (A). Hence, the general description of the multistage polymerization process described for the first heterophasic propylene copolymer (A) also applies to the second heterophasic propylene copolymer (B).
[0294] Hence, temperature, pressure, H2 / C3 ratio, C2 / C3 ratio and residence time in the four subsequent polymerisation reactors are adjusted accordingly to produce the second heterophasic propylene copolymer (B) as described above.
[0295] It is preferred that the operating temperature in the first polymerisation reactor, preferably the loop reactor, is in the range of 72 to 95 °C, more preferably in the range of 75 to 92 °C, still more preferably in the range of 77 to 90 °C.
[0296] Typically, the pressure in the first polymerisation reactor, preferably a loop reactor, is in the range of 20 to 80 bar, preferably 30 to 70 bar, for example 35 to 65 bar.
[0297] It is preferred that a propylene homopolymer is produced in the first polymerization reactor, preferably a loop reactor. Accordingly, it is preferred that the first propylene polymer fraction is a propylene homopolymer fraction.
[0298] Hydrogen is preferably added to the first polymerization reactor to control the molecular weight, i.e. the melt flow rate MFR 2 .
[0299] Preferably, the ratio of hydrogen to propylene (H2 / C3 ratio) in the first polypropylene reactor, preferably a loop reactor, is in the range of 35 to 100 mol / kmol, more preferably 50 to 75 mol / kmol.
[0300] It is preferred that the first propylene polymer fraction has a melt flow rate MFR in the range of 50 to 500 g / 10 min, preferably in the range of 75 to 350 g / 10 min, more preferably in the range of 100 to 250 g / 10 min. 2 .
[0301] It is preferred that the operating temperature in the second polymerisation reactor, preferably the first gas phase reactor, is in the range of 75 to 95 °C, more preferably in the range of 78 to 92 °C.
[0302] Typically, the pressure in the second polymerization reactor, preferably the first gas phase reactor, is in the range of 5 to 50 bar, preferably 15 to 40 bar.
[0303] It is preferred that a propylene homopolymer is produced in the second polymerization reactor, preferably the first gas phase reactor. Accordingly, it is preferred that the second propylene polymer fraction is a propylene homopolymer fraction.
[0304] Preferably, hydrogen is added in the second polymerization reactor to control the molecular weight, i.e. the melt flow rate MFR 2 .
[0305] Preferably, the ratio of hydrogen to propylene (H2 / C3 ratio) in the second polypropylene reactor (preferably the first gas phase reactor) is in the range of 10 to 50 mol / kmol, more preferably 15 to 35 mol / kmol.
[0306] It is preferred that the combined first and second propylene polymer fractions have a melt flow rate MFR in the range of 20 to 150 g / 10 min, preferably in the range of 30 to 100 g / 10 min, more preferably in the range of 40 to 75 g / 10 min. 2 (230°C, 2.16kg, ISO 1133).
[0307] It is preferred that the operating temperature in the third polymerisation reactor, preferably the second gas phase reactor, is in the range of 75 to 95 °C, more preferably in the range of 78 to 92 °C.
[0308] Typically, the pressure in the third polymerization reactor, preferably the second gas phase reactor, is in the range of 5 to 50 bar, preferably 15 to 40 bar.
[0309] In the third polymerization reactor (preferably the second gas phase reactor) a propylene ethylene copolymer is produced. Thus, the third propylene polymer fraction is a propylene ethylene copolymer fraction.
[0310] The ratio of ethylene to propylene (C2 / C3 ratio) in the third polymerization reactor (preferably the second gas phase reactor) is in the range of 100 to 500 mol / kmol, more preferably 150 to 300 mol / kmol.
[0311] Due to the high ethylene to propylene ratio (C2 / C3 ratio) the third propylene copolymer fraction is preferably an elastomeric block copolymer having a propylene rich portion and an ethylene rich portion.
[0312] Preferably, hydrogen is added in the third polymerization reactor to control the molecular weight, i.e., the melt flow rate MFR 2 .
[0313] Preferably, the ratio of hydrogen to ethylene (H2 / C2 ratio) in the third polymerization reactor (preferably the second gas phase reactor) is in the range of 5 to 40 mol / kmol, more preferably 10 to 30 mol / kmol.
[0314] It is preferred that the combined first, second and third propylene polymer fractions have a melt flow rate MFR in the range of 5 to 100 g / 10 min, preferably in the range of 10 to 75 g / 10 min, more preferably in the range of 15 to 50 g / 10 min. 2 (230°C, 2.16kg, ISO 1133).
[0315] It is preferred that the operating temperature in the fourth polymerisation reactor, preferably the third gas phase reactor, is in the range of 75 to 95 °C, more preferably in the range of 78 to 92 °C.
[0316] Typically, the pressure in the fourth polymerization reactor, preferably the third gas phase reactor, is in the range of 5 to 50 bar, preferably 15 to 40 bar.
[0317] In the fourth polymerization reactor (preferably the third gas phase reactor), a propylene ethylene copolymer is produced. Thus, the fourth propylene polymer fraction is a propylene ethylene copolymer fraction.
[0318] The ratio of ethylene to propylene (C2 / C3 ratio) in the fourth polymerization reactor (preferably the third gas phase reactor) is in the range of 100 to 500 mol / kmol, more preferably 150 to 300 mol / kmol.
[0319] Due to the high ethylene to propylene ratio (C2 / C3 ratio) the fourth propylene copolymer fraction is preferably an elastomeric block copolymer having a propylene rich portion and an ethylene rich portion.
[0320] Preferably, hydrogen is added in the fourth polymerization reactor to control the molecular weight, i.e., the melt flow rate MFR 2 .
[0321] Preferably, the ratio of hydrogen to ethylene (H2 / C2 ratio) in the fourth polymerization reactor (preferably the third gas phase reactor) is in the range of 3 to 35 mol / kmol, more preferably 5 to 25 mol / kmol.
[0322] It is preferred that the combined first, second, third and fourth propylene polymer fractions have a melt flow rate MFR in the range of 3.0 to 30 g / 10 min, preferably 4.0 to 25 g / 10 min, more preferably 5.0 to 20 g / 10 min. 2(230°C, 2.16kg, ISO 1133).
[0323] Further, the combined first, second, third and fourth propylene polymer fractions preferably have a total comonomer content, preferably ethylene (C2) content, in the range of 5.0 to 20.0 wt.-%, preferably more preferably 5.5 to 18.0 wt.-%, based on the total weight of the combined first, second, third and fourth propylene polymer fractions, as determined by quantitative 13 The results were determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy.
[0324] Preferably, the first propylene polymer fraction is present in an amount of 25 to 45 wt %, more preferably 30 to 40 wt %, based on the total weight of the first, second, third and fourth propylene polymer fractions combined. If present, the amount of polypropylene produced in the prepolymerization reactor is usually added to the amount of the first propylene polymer fraction.
[0325] Preferably, the second propylene polymer fraction is present in an amount of 30 to 50 wt%, more preferably 35 to 45 wt%, based on the total weight of the first, second, third and fourth propylene polymer fractions combined.
[0326] Preferably the third propylene polymer fraction is present in an amount of 5 to 25 wt%, more preferably 10 to 20 wt%, based on the total weight of the first, second, third and fourth propylene polymer fractions combined.
[0327] Preferably the fourth propylene polymer fraction is present in an amount of 3 to 20 wt%, more preferably 5 to 15 wt%, based on the total weight of the first, second, third and fourth propylene polymer fractions combined.
[0328] According to the present invention the second heterophasic propylene copolymer (B) is preferably obtained by a multistage polymerisation process as described above in the presence of a Ziegler-Natta catalyst system.
[0329] It should be understood that there is no particular limitation on the catalyst system as long as a Ziegler-Natta catalyst system is used.
[0330] Concerning suitable catalyst systems for the preparation of the heterophasic propylene copolymer (B) reference is made to e.g. WO 2014 / 023603, EP591224, WO 2012 / 007430, EP 2415790, EP 2610270, EP 2610271, EP 2610272, EP 2610273, EP 2960257 and EP 2960256, which are incorporated herein by reference.
[0331] In another embodiment the Ziegler-Natta catalyst system may be modified by polymerizing a vinyl compound in the presence of a catalyst system as described above for the Ziegler-Natta catalyst system preferably used for the polymerization of the first heterophasic propylene copolymer (A).
[0332] Vinyl plastomer (C)
[0333] The ethylene-based plastomer (C) is preferably a copolymer of ethylene with a comonomer unit selected from α-olefins having 3 to 12 carbon atoms, preferably from α-olefins having 4 to 10 carbon atoms, most preferably from 1-butene or 1-octene.
[0334] Vinyl plastomers are often added to further improve the impact properties of the composition.
[0335] Vinyl plastomers are typically polymerized in the presence of a metallocene catalyst.
[0336] For the polymerization, a solution polymerization process is generally used.
[0337] The vinyl plastomer (C) is preferably a pristine polymer.
[0338] The vinyl plastomer (C) preferably has one or more of the following properties, preferably all of the following properties:
[0339] - a melt flow rate MFR of 0.5 to 25.0 g / 10 min, preferably 0.8 to 20.0 g / 10 min 2 (190°C, 2.16kg, ISO 1133); and
[0340] -865 to 900 kg / m 3 , preferably 870 to 890 kg / m 3 density.
[0341] The vinyl plastomer (C) preferably has a melting temperature of 50 to 85°C, preferably 65 to 80°C.
[0342] Further, the ethylene-based plastomer preferably has a flexural modulus measured according to ISO 178 of not more than 100 MPa, preferably from 10 to 50 MPa.
[0343] Such vinyl plastomers are commercially available under the trade names Engage, Exact, Queo, Tafmer, and the like.
[0344] Inorganic filler (D)
[0345] The inorganic filler (D) is preferably talc.
[0346] The inorganic filler (preferably talc) (D) preferably has a median particle size d of 1.0 to 20.0 microns, preferably 1.5 to 15.0 microns before compounding. 50 .
[0347] Further, the inorganic filler (preferably talc) (D) preferably has a top-cut particle size of 5.0 to 50.0 microns, preferably 8.0 to 40.0 microns before compounding. 95 .
[0348] The median particle size and the top cut particle size can usually be derived from the technical information published by the supplier. However, they can also be measured by any suitable method for measuring particle size, such as Sedigraph analysis or laser diffraction.
[0349] Such inorganic fillers are commercially available.
[0350] Propylene homopolymer (E)
[0351] The optional propylene homopolymer (E) preferably has a very high melt flow rate MFR of 300 to 1500 g / 10 min, preferably 400 to 1300 g / 10 min, more preferably 500 to 1200 g / 10 min. 2 (230°C, 2.16kg, ISO 1133).
[0352] Further, the optional propylene homopolymer (F) preferably has a melting temperature Tm determined by DSC according to ISO 11357-3 of 150 to 170 °C, preferably 155 to 166 °C.
[0353] The optional propylene homopolymer (E) is preferably a virgin polymer.
[0354] Such propylene homopolymers are usually added to further improve the flow properties of the composition.
[0355] Such propylene homopolymers are commercially available.
[0356] additive
[0357] Additives are generally used in compositions according to the present invention. Preferably, the additive is selected from one or more of antioxidants, UV stabilizers, slip agents, nucleating agents, pigments, lubricants, masterbatch polymers and / or antifogging agents and combinations thereof. These additives are well known in the polymer industry, and their use is familiar to those skilled in the art. Any additive present can be added as a separate raw material or in a mixture with a carrier polymer (i.e., a so-called masterbatch).
[0358] The additive is typically present in the composition in an amount of 0.1 to 5.0 wt %, still more preferably 0.5 to 3.5 wt %, based on the total weight of the composition.
[0359] Products
[0360] In another aspect, the present invention relates to an article, preferably an injection molded article, more preferably an injection molded automotive article, comprising the composition as described above or below.
[0361] The article preferably exhibits an excellent balance of properties in terms of high dimensional stability (assessed as low shrinkage), high paint adhesion (assessed as coated area of failure or delamination) and good surface properties (e.g. low tiger stripes in MSE surface quality). In addition, the article preferably exhibits high toughness after processing, as evidenced by a low initial coefficient of linear thermal expansion (CLTE).
[0362] It is preferred that the article has a thickness of less than 50 mm. 2 , preferably 0 to 45 mm 2 In mm 2 Indicates the coating area that has failed or delaminated.
[0363] Further, the article preferably has a MSE surface quality of less than 5.0, more preferably from 1.0 to 4.8 at a filling time of 1.5 s.
[0364] Furthermore, the article preferably has a MSE surface quality at a filling time of 3 s below 4.5, more preferably in the range of 1.0 to 4.2.
[0365] Further, the article preferably has a MSE surface quality of less than 4.0, more preferably from 1.0 to 3.5 at a filling time of 6 s.
[0366] Furthermore, the article preferably has an isotropic area shrinkage of less than 1.0%, more preferably 0.75 to 0.95%.
[0367] Further, the article preferably has a coefficient of linear thermal expansion in the machine direction (CLTE 23-80°C, MD) in the temperature range of +23 to +80°C at a heating rate of 1°C / min of less than 95 μm / m°C, more preferably of 70 to 90 μm / m°C.
[0368] Furthermore, the article preferably has a coefficient of linear thermal expansion in the transverse direction (CLTE 23-80°C, TD) in the temperature range of +23 to +80°C at a heating rate of 1°C / min of less than 145 μm / m°C, more preferably of 110 to 140 μm / m°C.
[0369] Further, the article preferably has a coefficient of linear thermal expansion in the machine direction (CLTE-30-80°C, MD) in the temperature range of -30 to +80°C at a heating rate of 1°C / min of less than 75 μm / m°C, more preferably 50 to 75 μm / m°C.
[0370] Furthermore, the article preferably has a coefficient of linear thermal expansion in the transverse direction (CLTE-30-80°C, TD) in the temperature range of -30 to +80°C at a heating rate of 1°C / min of less than 125 μm / m°C, more preferably 100 to 120 μm / m°C.
[0371] Due to the excellent balance of properties, the article is suitable for use in both painted and unpainted automotive articles. Therefore, the article is very versatile and can be used in both automotive interior and exterior applications.
[0372] use
[0373] In another aspect, the present invention relates to the use of a composition as described above or below for injection moulding of an article, preferably an automotive article.
[0374] Experimental Section
[0375] The following examples are included to demonstrate certain aspects and embodiments of the invention described in the claims. However, those skilled in the art will appreciate that the following description is illustrative only and should not be viewed in any way as limiting the present invention.
[0376] Test Method
[0377] a) CRYSTEX
[0378] Determination of the crystalline and soluble fractions and their corresponding properties (IV and ethylene content)
[0379] The crystalline fraction (CF) and soluble fraction (SF) of the polypropylene (PP) composition as well as the comonomer content and intrinsic viscosity of the corresponding fractions were analyzed by using a CRYSTEX instrument Polymer Char (Valencia, Spain). Details of the technology and methods can be found in the literature (Ljiljana Jeremic, Andreas Albrecht, Martina Sandholzer & Markus Gahleitner (2020) Rapid characterization of high-impact ethylene-propylene copolymer composition by crystallization extraction separation: comparability to standard separation methods, International Journal of Polymer Analysis and Characterization, 25: 8, 581-596).
[0380] The crystalline and amorphous fractions were separated by temperature cycles of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. Quantification of SF and CF as well as determination of ethylene content (C2) were achieved by an integrated infrared detector (IR4) and for determination of intrinsic viscosity (iV) an online 2-capillary viscometer was used.
[0381] The IR4 detector is a multi-wavelength detector that measures two different wavelength bands (CH 3 Extension vibration (center is about 2960cm -1 ) and CH stretching vibration (2700-3000cm -1 )) is used to determine the concentration and ethylene content in ethylene-propylene copolymers. The IR4 detector is used with a known ethylene content in the range of 2 wt% to 69 wt% (given by 13 C-NMR measurement) and each having a series of 8 EP copolymers with different concentrations in the range of 2 to 13 mg / ml were calibrated. In order to simultaneously meet the two characteristic concentrations and ethylene content of various polymer concentrations expected during Crystex analysis, the following calibration equation was applied:
[0382] Conc=a+b*Abs(CH)+c*(Abs(CH)) 2 +d*Abs(CH 3 )+e*(Abs(CH 3 ) 2+f*Abs(CH)*Abs(CH 3 ) (Equation 1)
[0383] CH 3 / 1000C=a+b*Abs(CH)+c*Abs(CH 3 )+d*(Abs(CH 3 ) / Abs(CH))+e*(Abs(CH 3 ) / Abs(CH)) 2 (Equation 2)
[0384] Constants a to e in Equation 1 and constants a to f in Equation 2 are determined by using least squares regression analysis.
[0385] CH 3 / 1000C is converted to ethylene content (wt%) using the following relationship:
[0386] Weight % (ethylene in EP copolymer) = 100-CH 3 / 1000TC*0.3(Equation 3)
[0387] The amounts of the soluble fraction (SF) and the crystalline fraction (CF) are related by means of the XS calibration to the amount of "xylene cold solubles" (XCS) and the xylene cold insolubles (XCI) fraction, respectively, determined by the standard gravimetric method according to ISO 16152. The XS calibration was achieved by testing various EP copolymers with XS contents in the range of 2-31 wt%. The determined XS calibration is linear:
[0388] Weight %XS=1,01*weight %SF (Equation 4)
[0389] The intrinsic viscosity (iV) of the parent EP copolymer and its soluble fraction and crystalline fraction was determined using an online 2-capillary viscometer and correlated to the corresponding iV determined by the standard method in decalin according to ISO 1628-1. Various EP PP copolymers with iV = 2-4 dL / g were used for calibration. The calibration curve determined was linear:
[0390] iV(dL / g)=a*Vsp / c (Equation 5)
[0391] The sample to be analyzed is weighed at a concentration of 10 mg / ml to 20 mg / ml. In order to avoid the injection of gels and / or polymers such as PET and PA that may not dissolve in TCB at 160°C, the weighed sample is loaded into a stainless steel mesh of MW 0,077 / D 0,05 mmm.
[0392] After automatically filling the vial with 1,2,4-TCB containing 250 mg / l 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the sample was dissolved at 160°C with constant stirring at 400 rpm until complete dissolution was achieved, typically for 60 minutes. To avoid sample degradation, the polymer solution was covered with a N2 atmosphere during the dissolution process.
[0393] A defined volume of sample solution is injected into a column filled with an inert carrier, where crystallization of the sample and separation of the soluble fraction from the crystalline part are carried out. This process is repeated twice. During the first injection, the entire sample is measured at high temperature, and the iV [dl / g] and C2 [wt%] of the PP composition are determined. During the second injection, the soluble fraction (at low temperature) and the crystalline fraction (at high temperature) (wt% SF, wt% C2, iV) are measured under a crystallization cycle.
[0394] b) Xylene cold soluble fraction (XCS, weight %)
[0395] The xylene cold soluble fraction (XCS) is determined according to ISO 16152; first edition; 2005-07-01 at 25° C. The part that remains insoluble is the xylene cold insoluble (XCI) fraction.
[0396] c) Intrinsic viscosity
[0397] The intrinsic viscosity is measured according to DIN ISO 1628 / 1, October 1999 (in decalin at 135° C.).
[0398] d) Simply supported beam notched impact strength
[0399] According to ISO 179-1eA at +23°C and -20°C on 80×10×4 mm prepared according to EN ISO 1873-2 3 Determined on injection molded specimens. The specimens were measured after a conditioning time of 96 hours at 23°C.
[0400] e) Tensile properties
[0401] The tensile modulus, tensile elongation at yield and tensile elongation at break were measured according to ISO 527-2 (crosshead speed = 1 mm / min; test speed 50 mm / min, 23° C.) using injection molded specimens 1B (dog bone shape, 4 mm thickness) prepared as described in EN ISO 1873-2. The specimens were measured after a conditioning time of 96 hours at 23° C.
[0402] f) Instrument puncture test
[0403] According to ISO 6603-2:2000 at 23°C and -30°C in 60×60×3mm3 Instrumented penetration tests were performed on injection molded plaques. The specimens were measured after a conditioning time of 96 hours at 23°C, -20°C and -30°C.
[0404] g) Comonomer content
[0405] Poly(propylene-co-ethylene)-ethylene content-IR spectroscopy
[0406] Quantitative infrared (IR) spectroscopy was used to quantify the ethylene content of poly(ethylene-co-propylene) copolymers by calibration to the primary method. Calibration was facilitated by using a set of in-house non-commercial calibration standards that have the ability to quantify the ethylene content of poly(ethylene-co-propylene) copolymers by calibration to the primary method. 13 The known ethylene content was determined by C solution state nuclear magnetic resonance (NMR) spectroscopy. The calibration procedure was performed in a conventional manner well documented in the literature. The calibration set consisted of 38 calibration standards with ethylene contents ranging from 0.2 to 75.0 wt % produced at pilot or full scale under various conditions. The calibration set was selected to reflect the typical copolymer types encountered in the final quantitative IR spectroscopy.
[0407] Quantitative IR spectra were recorded in the solid state using a Bruker Vertex 70 FTIR spectrometer. The spectra were recorded on 25×25 mm square films of 300 μm thickness, prepared by compression molding at 180–210 °C and 4–6 MPa. For samples with very high ethylene content (>50 mol%), 100 μm thick films were used. Standard transmission FTIR spectroscopy was employed using a 5000–500 cm -1 spectral range, 6mm aperture, 2cm -1 spectral resolution, 16 background scans, 16 spectral scans, interferogram zero filling factor of 64 and Blackmann-Harris 3-term apodisation. -1 CH 2 The total area of sway deformation (A Q ) was quantitatively analyzed, which corresponds to (CH 2 ) >2 Structural unit (integration method G, limits 762 and 694 cm -1 ). The quantitative band was normalized to 4323 cm -1 The area of the CH band at R ), which corresponds to the CH building block (integration method G, limits 4650, 4007 cm -1 ). Then a secondary calibration curve was used to normalize the absorbance (A Q / A R) predicts the ethylene content in weight percent. The calibration curve has been previously constructed by ordinary least squares (OLS) regression of the normalized absorbance measured on the calibration set and the main comonomer content.
[0408] Poly(propylene-co-ethylene)-ethylene content- 13 C NMR spectroscopy
[0409] Use for 1 H and 13 Quantitative measurements were recorded in solution on a Bruker Avance III 400 NMR spectrometer operating at 400.15 and 100.62 MHz, respectively. 13 C{ 1 H} NMR spectroscopy. Nitrogen was used for all pneumatics and all spectra were 13 C optimized 10 mm extended temperature probe was recorded at 125 °C. Approximately 200 mg of material was mixed with chromium (III) acetylacetonate (Cr(acac) 3 ) were dissolved in 3 ml of 1,2-tetrachloroethane-d 2 (TCE-d 2 ) to obtain a 65 mM solution of the relaxing agent in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475).
[0410] To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after initial sample preparation in a heating block. After insertion of the magnet, the tube rotated at 10 Hz. This setting was selected mainly for high resolution and accurate quantification of ethylene content and quantitatively required for this setting. Standard single pulse excitation without NOE was used, using an optimized tip angle, a 1 s recycle delay and a double-stage WALTZ16 decoupling scheme (Zhou, Z. et al., J. Mag. Reson. 187 (2007) 225, and Busico, V. et al., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were collected for each spectrum. For quantitative 13 C{ 1H} NMR spectra are processed, integrated and the relevant quantitative properties are determined by integration. Using the chemical shift of the solvent, all chemical shifts are indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00ppm. Even if the structural unit does not exist, this method allows comparable references. Observed the characteristic signal corresponding to the incorporation of ethylene (Cheng, HN, Macromolecules 17 (1984), 1950), the comonomer fraction is calculated as the fraction of ethylene in the polymer relative to all monomers in the polymer:
[0411] f E =(E / (P+E)
[0412] Using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157), the 13 C{ 1 The comonomer fraction is quantified by integrating multiple signals over the entire spectral area in the H} spectrum. This method was chosen because of its robustness and ability to account for the presence of regional defects when needed. The integration area was slightly adjusted to improve applicability over the entire range of comonomer content encountered. For systems with very low ethylene content where only isolated ethylene in the PPEPP sequence was observed, the method of Wang et al. was modified to reduce the impact of the integration of sites that are no longer present. This method reduces the overestimation of ethylene content in such systems and is achieved by reducing the number of sites used to determine the absolute ethylene content to:
[0413] E=0.5(S ββ +S βγ +S βδ +0.5(S αβ +S αγ ))
[0414] By using this set of sites, the corresponding integral equation becomes:
[0415] E=0.5(I H +I G +0.5(I C +I D ))
[0416] The same symbols used in the article by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) are used. The equation for absolute propylene content is not modified. The mole percentage of comonomer incorporation is calculated from the mole fraction:
[0417] E[mol%]=100*f E
[0418] Calculate the weight percent of comonomer incorporation from the mole fraction:
[0419] E[wt%]=100*(f E *28.06) / ((f E *28.06)+((1-f E )*42.08))
[0420] h)MFR
[0421] Melt flow rate is measured at 230°C (polypropylene-based materials) or 190°C (polyethylene-based materials) with a load of 2.16 kg (MFR 2 ). The melt flow rate is the amount of polymer (expressed in grams) which a test apparatus standardized according to ISO 1133 extrudes within 10 minutes under a load of 2.16 kg at a temperature of 230° C. (or 190° C.).
[0422] i) Density
[0423] Density was measured according to ISO 1183-187. Sample preparation was done by compression molding according to ISO 1872-2:2007.
[0424] j)DSC analysis, melting temperature (T m ) and crystallization temperature (T c )
[0425] The measurements were performed on 5 to 7 mg samples using a TA Instrument Q200 Differential Scanning Calorimeter (DSC). The DSC was run according to ISO 11357 / Part 3 / Method C2 with a heating / cooling / heating cycle in the temperature range of -30 to +225°C at a scanning rate of 10°C / min. The crystallization temperature (T c ) and crystallization enthalpy (H c ) is determined by the cooling step, while the melting temperature (T m ) and melting enthalpy (H m ) is determined by the second heating step.
[0426] k) Heat Deformation Temperature (HDT)
[0427] HDT is prepared according to ISO 1873-2 and stored at +23°C for at least 96 hours before measurement. 3 Determined on injection molded specimens. Tests were performed according to ISO 75, Condition B, on flat supported specimens at a nominal surface stress of 0.45 MPa.
[0428] l) Coefficient of linear thermal expansion (CLTE)
[0429] The coefficient of linear thermal expansion (CLTE) is determined according to ISO 11359-2: 1999 on 20 10 mm long pieces cut from the same injection molded specimens used for the tensile modulus determination. The measurements are carried out in the temperature range of -30 to +80°C at a heating rate of 1°C / min and in the temperature range of 23 to +80°C at a heating rate of 1°C / min in the longitudinal direction.
[0430] m) Paint Adhesion
[0431] Adhesion is characterized by the resistance of a decorative coating (such as paint) to washing with a high pressure washer under the specific conditions described below.
[0432] Injection molded sample plaques (150 mm × 80 mm × 3 mm) were produced at a melt temperature of 240°C and a mold temperature of 50°C. The flow front speed was 100 mm / s. Before coating, the Zeller Gmelin The plate was cleaned for 5 minutes at 1000 mm / s. Subsequently, the surface was activated by combustion, where a burner sprayed a mixture of propane (9 l / min) and air (180 l / min) in a ratio of 1:20 onto the polymer substrate at a speed of 670 mm / s. Afterwards, 3 layers were applied onto the polymer substrate, namely primer, base coat (black) and clear coat. The combustion step was performed twice.
[0433] The decorative coating was cut down to the substrate using a cutting tool to a total depth of about 500 μm (including coating and substrate), forming a cross with 100 mm long branches. On each coated substrate, 3 lines with corresponding crosses were cut. The cut area was further exposed to hot water vapor at temperature T, which was directed to the test panel surface at a distance d at an angle α for a duration t. The pressure of the water jet is generated by the water flow rate and is determined by the type of nozzle installed at the end of the water pipe.
[0434] Use the following parameters:
[0435] T(water)=68°C; t=30s; d=100mm, α=90°, water pressure 65 bar, nozzle type=Walter 13 / 32.
[0436] By quantifying the coating area (in mm) of failure or delamination on each test line 2Adhesion was evaluated by measuring the failure area of the 3 test lines on the 5 specimens (i.e., the average of the 15 test points in total) using the standard deviation (SD). For each sample, 5 panels (150 mm × 80 mm × 3 mm) have been tested. For this purpose, images of the test lines before and after steam jet exposure were taken. The delamination area was then calculated using image processing software. The average failure area of the 3 test lines on the 5 specimens (i.e., the average of the 15 test points in total) was reported as the average failure area. SD is the standard deviation, which is determined according to the following equation:
[0437]
[0438] in:
[0439] x is the observed value;
[0440] is the mean of the observed values;
[0441] n is the number of observations.
[0442] n) Tiger stripes (MSE) or flow marks
[0443] The tendency to show flow marks was checked using the method described below. The method is described in detail in WO 2010 / 149529, the entire contents of which are incorporated herein. The surface quality was characterized using an optical measurement system described by Sybille Frank et al. in PPS25 Intern. Conf. Polym. Proc. Soc 2009 or Proceedings of the SPIE, Vol. 6831, pp. 68130T-68130T-8 (2008).
[0444] The method consists of the following two aspects:
[0445] 1. Image recording:
[0446] The basic principle of the measurement system is to illuminate the board with a defined light source (LED) in a closed environment and record the image with a CCD camera system.
[0447] 2. Image analysis:
[0448] The specimen is flood-illuminated from one side and the upwardly reflected part of the light is deflected by two mirrors to a CCD sensor. The gray value image thus created is analyzed line by line. The mean square error (MSE) is calculated from the recorded gray value deviations and thus the surface quality is quantified, i.e. the larger the MSE value, the more obvious the surface defects. In general, for one and the same material, the tendency for flow marks increases when the injection speed increases.
[0449] For this evaluation, a 440 × 148 × 2.8 mm film with texture VW K50 and a 1.4 mm film gate was used. 3and produced these panels with different filling times of 1.5, 3 and 6 seconds, respectively.
[0450] Other conditions:
[0451] Melting temperature: 240℃.
[0452] Mould temperature 30℃.
[0453] Dynamic pressure: 10 bar hydraulic
[0454] At a specific filling time, the smaller the MSE value, the smaller the tendency of flow marks.
[0455] o) Isotropic area shrinkage
[0456] The area shrinkage is calculated based on shrinkage data determined on a sector plate with a radius of 320 mm, an opening angle of 20° and a thickness of 2.8 mm, produced by injection molding using an Engel ES1350 / 350 machine and with a 7.6×2.8 mm diameter at the bottom of the sector. 2 A melt temperature of 240°C, a mold temperature of 25°C and a fill time of 3.5 seconds were used, followed by a hold time of 20 seconds at a hold pressure of 400 bar.
[0457] Instead of measuring the outer dimensions of the board, a dot pattern is formed on the board by etching spots with a diameter of 1 mm at distances between 5 and 10 mm. Immediately after demoulding, the original pattern is recorded by the OGPSmartscope Flash 400 optical measurement system and used as a dimensional reference. After 96 hours at 23°C, the molded pattern after shrinkage is determined and all deviations in the point-to-point distances are recorded. To calculate the isotropic area shrinkage, multiple measurement points are connected with a vector and the resulting area is determined, where A is the area after 96 hours and A is the area after 96 hours. 0 is the area before this period. Then the isotropic area shrinkage rate S iso Calculated as
[0458]
[0459] experiment
[0460] Preparation of HECO A1-A6 and HECO B
[0461] Catalyst system:
[0462] For the polymerization process of HECO A-1 to HECO A-6, a Ziegler-Natta type catalyst (ZN1) as used in the inventive examples of WO 2016 / 066446 A1 and described as prepolymerized with vinylcyclohexane to achieve nucleation with poly(vinylcyclohexane) was used.
[0463] Nucleation by prepolymerization using vinylcyclohexane is described in detail in EP 2 960 256 B1 and EP 2 960 279 B1. These documents are incorporated herein by reference.
[0464] For the polymerization process of HECO B, the conventional high-yield MgCl 2 Supported Ziegler-Natta polypropylene catalyst component (ZN2) comprising diethyl phthalate as internal donor. Catalyst components and their preparation concepts are generally described, for example, in patent publications EP491566, EP591224 and EP586390.
[0465] Therefore, the catalyst component was prepared as follows: First, 0.1 mol of MgCl2 x 3EtOH was suspended in 250 ml of decane in an atmospheric pressure reactor under inert conditions. The solution was cooled to -15°C and 300 ml of cold TiCl was added while the temperature was maintained at that temperature. 4 Then, the temperature of the slurry was slowly raised to 20°C. At this temperature, 0.02 mol of dioctyl phthalate (DOP) was added to the slurry. After the addition of the phthalate, the temperature was raised to 135°C within 90 minutes and the slurry was allowed to stand for 60 minutes. Then, 300 ml of TiCl 4 and the temperature was maintained at 135° C. for 120 minutes. Thereafter, the catalyst was filtered from the liquid, and the catalyst was washed six times with 300 ml of heptane at 80° C. Then, the solid catalyst component was filtered and dried.
[0466] Polymerization of HECO A1-A6 and HECO B
[0467] HECO A1-A6 and HECO B were prepared in a prepolymerization / loop reactor / gas phase reactor 1 / gas phase reactor 2 / gas phase reactor 3 configuration followed by a pelletizing step. The above defined catalyst system was used in combination with triethylaluminum (TEAL) as cocatalyst and dicyclopentadienyldimethoxysilane (donor D) as external donor.
[0468] HECO A1-A5 produced polymer powders with an elastomeric phase (expressed as XCS content) higher than 30 wt.-% and a melt flow rate of about 15 to 40 g / 10 min. In order to reduce the elastomeric phase (XCS content) to an amount below 30 wt.-% and to increase the melt flow rate, the polymer powders of HECO A1-A5 were diluted with a high flow propylene homopolymer similar to the propylene homopolymer produced as matrix material in the loop reactor and in the gas phase reactor 1. The weights of the respective polymer powders and the propylene homopolymer blended in the dilution step and the melt flow rate of the propylene homopolymer are shown in Table 1 below.
[0469] The diluted HECO A1-A5 resins, the polymer powder of HECO A6 and the polymer powder of HECO B were compounded in a co-rotating twin-screw extruder Coperion ZSK 47 at 220°C with 0.15 wt% antioxidant (Irganox B215FF from BASF AG, Germany; this is a 1:2 mixture of pentaerythritol tetrakis(3-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate (CAS No. 6683-19-8) and tris(2,4-di-tert-butylphenyl) phosphite (CAS No. 31570-04-4)), 0.05 wt% calcium stearate (CAS No. 1592-23-0, commercially available from Faci, Italy). CRYSTEX QC analysis and other properties of these copolymers gave the results listed in Table 2.
[0470] Table 1: Preparation of HECO A1-A6 and HECO B
[0471]
[0472]
[0473] nd = not determined; na = not applicable
[0474] b) Performance of HECO A1-A7
[0475] HECO A7 is a heterophasic propylene copolymer with a melt flow rate MFR 2 (ISO 1133, 230°C / 2.16 kg) is 50 g / 10 min and is commercially available from Borealis AG as BH348MO.
[0476] Table 2: CRYSTEX QC analysis and other properties of HECO A1-A7
[0477]
[0478] *From the product data sheet of BH348MO
[0479] c) Preparation of the compositions of Examples IE1, IE2 and CE1-CE5
[0480] Other components:
[0481] Plastomer C is Queo 8203, an ethylene-1-octene plastomer with a density of 883 kg / m 3 , MFR 2 (2.16 kg, 190° C., ISO 1133) is 3 g / 10 min and is commercially available from Borealis AG.
[0482] Talc D is Luzenac HAR T84, its d 50 2.0 μm, d 95 10.0 μm (Sedigraph measurement), commercially available from IMERYS.
[0483] PP-Homo E is a commercial propylene homopolymer HL708FB, with MFR 2 (2.16 kg, 230° C., ISO 1133) is 800 g / 10 min, Tm (DSC, ISO 11357-3) is 158° C., and is commercially available from Borealis AG.
[0484] The final composition was compounded in a Coperion ZSK40 twin screw extruder at 220°C using polymer and talc as well as antioxidants, UV stabilizers, slip agents, nucleating agents, carbon black masterbatch, calcium stearate, anti-fogging agents. The composition of the examples is shown in Table 3.
[0485] Table 3: Composition of Examples
[0486]
[0487] *Tris(2,4-di-tert-butylphenyl) phosphite, CAS No. 31570-04-4,
[0488] **Pentaerythritol tetrakis(3-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate, CAS No. 6683-19-8
[0489] d) Properties of the compositions of Examples IE1, IE2 and CE1-CE5
[0490] Table 4 shows the performance of the examples.
[0491] Table 4: Performance of the examples
[0492] CE1 CE2 C3 IE1 IE2 CE4 CE5 <![CDATA[MFR 2 ,g / 10min]]> 34.2 39.5 44.5 40.7 32.7 22.5 24.1 C2 (composition), weight % 16.5 17.7 18.3 20.4 23.4 18.1 18.9 iV(composition),dl / g 1.5 1.5 1.5 1.6 1.7 1.5 1.7 CF (CRYSTEX), weight% 73.8 71.7 71.8 71.6 71.8 71.6 72.5 C2(CF), weight% 3.5 3.7 4.2 5.3 8.4 4.5 4.9 iV(CF),dl / g 1.3 1.2 1.2 1.3 1.3 1.2 1.4 SF (CRYSTEX), weight% 26.2 28.3 28.2 28.4 28.2 28.4 27.5 C2(SF), weight% 53.2 53.2 55.2 59.2 63.1 54.3 56.6 iV(SF),dl / g 2.2 2.3 2.4 2.4 2.5 2.3 2.4 Tensile modulus, MPa 1925 2015 2089 2091 2068 2018 1990 Yield elongation, % 5.30 3.71 3.35 3.23 3.22 3.62 3.89 Elongation at break, % 38.85 16.78 10.96 9.18 9.75 14.80 30.23 <![CDATA[Simply supported beam NIS, +23°C, kJ / m 2 > 9.85 9.59 8.76 8.37 7.54 9.33 10.23 <![CDATA[Simply supported beam NIS, -20 °C, kJ / m 2 > 3.53 4.19 4.29 4.37 4.23 4.01 4.29 Energy at maximum force, +23℃, J 24.25 23.84 23.96 23.90 23.42 22.54 24.05 Puncture energy, +23℃, J 37.79 39.63 36.61 31.91 36.66 34.23 44.19 Energy at maximum force, -20℃, J 2.64 6.27 5.41 6.77 10.14 6.26 16.18 Puncture energy, -20℃, J 2.79 6.55 5.64 7.08 10.56 6.64 16.73 Energy at maximum force, -30℃, J 1.15 2.70 2.59 3.76 4.80 2.38 5.55 Puncture energy, -30℃, J 1.23 2.84 2.76 3.88 5.04 2.50 6.69 CLTE,+23 / 80℃,μm / m℃,MD 84.14 81.30 77.26 81.06 82.03 82.19 76.44 CLTE,+23 / 80℃,μm / m℃,TD 134.5 130.8 138.4 129.8 136.6 130.7 135.4 CLTE,-30 / 80℃,μm / m℃,MD 70.53 68.42 64.50 67.47 68.49 68.78 60.81 CLTE,-30 / 80℃,μm / m℃,TD 112.9 111.2 108.5 110.5 116.2 111.0 108.5 MSE surface quality, 1,5s 20.8 10.0 5.7 4.2 3.9 7.6 10.3 MSE surface quality, 3s 12.8 6.2 4.7 3.7 3.1 5.8 7.3 MSE surface quality, 6s 4.5 3.3 3.2 3.0 2.6 3.3 4.0 Isotropic area shrinkage, % 0.95 0.91 0.89 0.88 0.87 0.91 0.84 <![CDATA[Layered painted area, mm 2 > 46.8 52.6 54.2 42.4 4.0 52.6 57.3
[0493] Inventive Examples IE1 and IE2, which comprise heterophasic copolymers of propylene A with an ethylene content C2(SF) of the soluble fraction within the claimed range, HECO A4 and HECO A5 show an improved balance of properties with lower MSE surface quality, smaller paint delamination area and increased puncture energy (especially at low temperatures) at comparable tensile properties, impact properties, CLTE and shrinkage.
[0494] These improvements include Figures 1 to 3 shown.
[0495] Figure 1 The improvement in the paint delamination area is shown depending on the ethylene content C2(SF) of the soluble fraction (C2(SF)BaseHECO) of the corresponding HECO A1-A5 used in comparative examples CE1-CE3 and inventive examples IE1 and IE2.
[0496] Figure 2 Graphed is the improvement in the puncture energy in the instrumented puncture test at -30°C (IPT-30°C) depending on the ethylene content C2(CF) of the crystalline fraction (C2(CF) Compound) of the compositions of Comparative Examples CE1-CE3 and Inventive Examples IE1 and IE2.
[0497] Figure 3 The improvement in MSE surface quality at a fill time of 3 seconds (MSE 3s) is shown as a function of the improvement in puncture energy in the instrumented puncture test at -20°C (IPT-20°C) for the compositions of Comparative Examples CE1-CE3 and Inventive Examples IE1 and IE2.
[0498] Therefore, the compositions of Inventive Examples IE1 and IE2 are suitable for use in both painted and unpainted automotive applications.
Claims
1. A composition suitable for automotive applications The composition can be obtained by blending at least components (A), (B), (C) and (D) (A) 30 to 50 wt.-%, preferably 33 to 48 wt.-%, more preferably 35 to 45 wt.-% of the first heterophasic propylene copolymer; (B) 10 to 25 wt.-%, preferably 12 to 22 wt.-%, more preferably 14 to 20 wt.-% of a second heterophasic propylene copolymer; (C) 5 to 15 wt %, preferably 10 to 14 wt %, more preferably 10 to 13 wt % of ethylene-based plastomer and (D) 5 to 20 wt %, preferably 7 to 18 wt %, more preferably 8 to 17 wt % of an inorganic filler; wherein all percentages refer to the total composition, and wherein The first heterophasic propylene copolymer (A) comprises a matrix phase and an elastomeric phase dispersed therein and has - a melt flow rate MFR2 (230°C, 2.16 kg, ISO 1133) of 60 to 250 g / 10 min, preferably 63 to 200 g / 10 min, more preferably 65 to 180 g / 10 min; - a soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of 15.0 to 30.0 wt.-%, preferably 17.5 to 27.5 wt.-%, more preferably 20.0 to 25.0 wt.-%; - in the range of 40.0 wt % to 75.0 wt %, preferably 42.5 wt % to 70.0 wt %, more preferably 44.0 wt % to 65.0 wt % by quantitative 13 the ethylene content C2(SF) of the soluble fraction determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy; and - an intrinsic viscosity iV(SF) of the soluble fraction measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 2.0 to 4.5 dl / g, preferably 2.3 to 4.0 dl / g, more preferably 2.5 to 3.5 dl / g; The second heterophasic propylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein and has - a melt flow rate MFR2 (230°C, 2.16 kg, ISO 1133) of 3.0 to 30 g / 10 min, preferably 4.0 to 25 g / 10 min, more preferably 5.0 to 20 g / 10 min; - a xylene cold soluble (XCS) fraction in the range of 18.0 to 45.0 wt.-%, preferably 20.0 to 40.0 wt.-%; and - an intrinsic viscosity iV(XCS) of the XCS fraction measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 2.5 to 8.5 dl / g, preferably 3.0 to 8.0 dl / g, more preferably 3.5 to 7.5 dl / g; The vinyl plastomer (C) is a copolymer of ethylene and a comonomer unit, wherein the comonomer unit is selected from α-olefins having 3 to 12 carbon atoms, preferably from α-olefins having 4 to 10 carbon atoms, most preferably from 1-butene or 1-octene, and the vinyl plastomer (C) has - a melt flow rate MFR2 (190° C., 2.16 kg, ISO 1133) of 0.5 to 25.0 g / 10 min, preferably 0.8 to 20.0 g / 10 min; and -865 to 900 kg / m 3 , preferably 870 to 890 kg / m 3 density; and The composition has - a melt flow rate MFR2 (230°C, 2.16 kg, ISO 1133) of 15 to 80 g / 10 min, preferably 18 to 70 g / 10 min, more preferably 20 to 60 g / 10 min.
2. The composition according to claim 1, which can be obtained by blending components (A), (B), (C), (D) and component (E) 5 to 16 wt%, preferably 7 to 15 wt%, more preferably 8 to 14 wt% of propylene homopolymer; wherein all percentages refer to the total composition, and wherein The propylene homopolymer (E) has - a melt flow rate MFR2 (230° C., 2.16 kg, ISO 1133) of 300 to 1500 g / 10 min, preferably 400 to 1300 g / 10 min, more preferably 500 to 1200 g / 10 min.
3. The composition according to claim 1 or 2, wherein the inorganic filler (D) is talc, having - a pre-compounding median particle size d of 1.0 to 20.0 microns, preferably 1.5 to 15.0 microns 50 ; and / or - a pre-compounding top cut particle size d of 5.0 to 50.0 microns, preferably 8.0 to 40.0 microns 95 .
4. Composition according to anyone of claims 1 to 3, wherein the first heterophasic propylene copolymer (A) has one or more, preferably all of the following properties: - a crystalline fraction (CF) content determined according to CRYSTEX QC analysis in the range of 70.0 to 85.0 wt.-%, more preferably 72.5 to 82.5 wt.-%, still more preferably 75.0 to 80.0 wt.-%; and / or -3.0 to 20.0 wt%, preferably 3.5 to 15.0 wt%, more preferably 4.0 to 12.0 wt% by quantitative 13 the ethylene content C2(CF) in the crystalline fraction determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy; and / or - an intrinsic viscosity iV(CF) of the crystalline fraction measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 0.7 to 1.7 dl / g, preferably 0.8 to 1.5 dl / g, more preferably 0.9 to 1.4 dl / g; and / or - a ratio of the intrinsic viscosity of the soluble fraction to the crystalline fraction (iV(SF) / iV(CF)) of from 2.2 to 3.0, preferably from 2.4 to 2.9, more preferably from 2.6 to 2.8; and / or - a ratio of the ethylene content of the soluble fraction to the crystalline fraction (C2(SF) / C2(CF)) in the range of 3.0 to 12.0, more preferably in the range of 4.0 to 11.0, still more preferably in the range of 5.0 to 10.0; and / or - 10.0 to 30.0 wt. %, preferably 11.0 to 25.0 wt. %, more preferably 12.5 to 22.5 wt. % by weight 13 the total content of units derived from ethylene (C2) determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy; and / or - a melting temperature Tm measured by differential scanning calorimetry (DSC) according to ISO 11357 / part 3 / method C2 of 155 to 175°C, preferably 157 to 172°C, more preferably 160 to 170°C; and / or - a crystallization temperature Tc measured by differential scanning calorimetry (DSC) according to ISO 11357 / part 3 / method C2 of 120 to 140°C, preferably 122 to 137°C, more preferably 125 to 135°C; and / or - a tensile modulus of 1200 to 1750 MPa, preferably 1250 to 1650 MPa, more preferably 1300 to 1500 MPa, measured according to ISO 527-2 (crosshead speed = 1 mm / min; test speed 50 mm / min, at 23°C) using injection molded test specimens 1B (dog bone shape, 4 mm thickness) prepared as described in EN ISO 1873-2; and / or -1.0 to 5.0 kJ / m 2 , preferably 1.3 to 3.5 kJ / m 2 80×10×4 mm prepared according to EN ISO 1873-2 at +23°C and -20°C according to ISO 179-1eA 3 Charpy notched impact strength at 23°C (CNIS at 23°C) measured on injection molded specimens; and / or -1.0 to 6.0 kJ / m 2 , preferably 1.3 to 5.0 kJ / m 2 80×10×4 mm prepared according to EN ISO 1873-2 at +23°C and -20°C according to ISO 179-1eA 3 Charpy notched impact strength at -20°C (CNIS at -20°C) measured on injection molded specimens; and / or - a coefficient of linear thermal expansion in the longitudinal direction (CLTE 23-80°C, MD) determined in accordance with ISO 11359-2:1999 in a temperature range of 23 to +80°C at a heating rate of 1°C / min of 115 to 150 μm / m°C, preferably 120 to 140 μm / m°C; and / or - a coefficient of linear thermal expansion in the transverse direction (CLTE 23-80°C, TD) determined in a temperature range of 23 to +80°C at a heating rate of 1°C / min according to ISO 11359-2:1999 of from 130 to 160 μm / m°C, preferably from 135 to 150 μm / m°C; and / or -105 to 140 μm / m°C, preferably 110 to 130 μm / m°C, coefficient of linear thermal expansion in the longitudinal direction (CLTE-30-80°C, MD), determined in accordance with ISO 11359-2:1999 in a temperature range of -30 to +80°C at a heating rate of 1°C / min; and / or -120 to 155 μm / m°C, preferably 125 to 145 μm / m°C, coefficient of linear thermal expansion in the transverse direction (CLTE-30-80°C, TD), determined according to ISO 11359-2:1999 in the temperature range of -30 to +80°C at a heating rate of 1°C / min; and / or -0.5 to 5.0 J, preferably 0.7 to 3.5 J according to ISO 6603-2:2000 at 23°C and -30°C in 60×60×3 mm 3 The puncture energy in the instrumented puncture test at 23°C (IPT 23°C) measured on injection moulded plaques; and / or -0.5 to 5.0 J, preferably 1.0 to 3.5 J according to ISO 6603-2:2000 at 23°C and -30°C in 60×60×3 mm 3 Puncture energy in the instrumented puncture test at -20°C (IPT-20°C) measured on injection molded plaques; and / or -80 to 105°C, preferably 85 to 100°C in a 80×10×4 mm glass prepared according to ISO 1873-2 3 Heat distortion temperature HDT B measured on injection moulded specimens.
5. The composition according to any one of claims 1 to 4, having - a crystalline fraction (CF) content determined according to CRYSTEX QC analysis in the range of 55.0 to 80.0 wt.-%, preferably 60.0 to 77.0 wt.-%, more preferably 65.0 to 75.0 wt.-%; and - a soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of 20.0 to 45.0 wt.-%, preferably 23.0 to 40.0 wt.-%, more preferably 25.0 to 35.0 wt.-%.
6. The composition according to claim 5, wherein - the crystalline fraction (CF) has a content of 4.5 to 12.0 wt. %, preferably 4.8 to 10.0 wt. %, more preferably 5.0 to 9.0 wt. % by weight of 13 Ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy; and / or - the crystalline fraction (CF) has an intrinsic viscosity (iV(CF)) measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 0.9 to 3.0 dl / g, preferably 1.0 to 2.8 dl / g, more preferably 1.1 to 2.5 dl / g; and / or - the soluble fraction (SF) has a content of 55.0 to 70.0 wt. %, preferably 57.0 to 67.5 wt. %, more preferably 58.0 to 65.0 wt. % by quantitative 13 Ethylene content (C2(SF)) determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy; and / or the soluble fraction (SF) has an intrinsic viscosity (iV(SF)) measured in decalin at 135° C. according to DIN ISO 1628 / 1 of 1.8 to 4.0 dl / g, preferably 2.0 to 3.5 dl / g, more preferably 2.3 to 3.3 dl / g; and / or - The composition is quantitatively 13 The total content of units derived from ethylene (C2), determined by FT-IR spectroscopy calibrated with C-NMR spectroscopy, is from 18.0 to 32.0% by weight, preferably from 19.0 to 30.0% by weight, more preferably from 20.0 to 28.0% by weight.
7. The composition according to any one of claims 1 to 6, having - a tensile modulus of from 1750 MPa to 2500 MPa, preferably from 1800 MPa to 2300 MPa; and / or - a tensile elongation at yield of 2.0 to 5.0%, preferably 3.0 to 4.0%; and / or - a tensile elongation at break of 6.5 to 20.0%, preferably 8.0 to 15.0%, All above properties were measured according to ISO 527-2 (crosshead speed = 1 mm / min; test speed 50 mm / min, at 23°C) using injection molded test specimens 1B (dog bone shape, 4 mm thickness) prepared as described in EN ISO 1873-2.
8. A composition according to any one of claims 1 to 7 having a mass fraction of 6.0 kJ / m 2 Up to 20.0kJ / m 2 , preferably 6.5 kJ / m 2 Up to 15.0kJ / m 2 Charpy notched impact strength at 23°C and / or 3.5 kJ / m 2 Up to 10.0kJ / m 2 , preferably 3.8 kJ / m 2 Up to 8.5 kJ / m 2 Charpy notched impact strength at -20°C, all the above properties are measured according to ISO 179-1eA at +23°C and -20°C on 80×10×4mm prepared according to EN ISO 1873-2 3 Measured on injection molded specimens.
9. The composition according to any one of claims 1 to 8, having a puncture energy of 25.0 to 55.0 J, preferably 28.0 to 50.0 J and / or an energy at maximum force of 15.0 to 45.0 J, preferably 18.0 to 35.0 J, when measured in an instrumented puncture test according to ISO 6603-2 at 23°C, and / or a puncture energy of 6.6 to 18.0 J, preferably 6.8 to 15.0 J and / or an energy at maximum force of 6.0 to 17.0 J, preferably 6.5 to 14.0 J, when measured in an instrumented puncture test according to ISO 6603-2 at -20°C, and / or a puncture energy of 10.0 to 15.0 J, preferably 10.0 to 17.0 J, preferably 10.0 to 18.0 J, when measured in an instrumented puncture test according to ISO 6603-2 at -30°C. 6603-2 has a puncture energy of 3.0 to 12.0 J, preferably 3.3 to 10.0 J and / or an energy at maximum force of 3.0 to 12.0 J, preferably 3.3 to 10.0 J, when measured in an instrumented puncture test.
10. An article, preferably an injection molded article, more preferably an injection molded automotive article, comprising the composition according to any one of claims 1 to 9.
11. The article according to claim 10, having a thickness of less than 50 mm 2 , preferably 0 to 45 mm 2 The value is evaluated in mm 2 Paint adhesion representing the coating area of failure or delamination, determined as described in the Experimental Section.
12. The article according to claim 10 or 11, having a MSE surface quality of less than 5.0, preferably from 1.0 to 4.8 at a filling time of 1.5 seconds, and / or a MSE surface quality of less than 4.5, preferably from 1.0 to 4.2 at a filling time of 3 seconds, and / or a MSE surface quality of less than 4.0, preferably from 1.0 to 3.5 at a filling time of 6 seconds, as determined as described in the experimental part.
13. The article according to any one of claims 10 to 12, having an isotropic shrinkage of less than 1.0%, preferably between 0.75 and 0.95%, as determined as described in the experimental part.
14. The article according to any one of claims 10 to 13, having a coefficient of linear thermal expansion in the longitudinal direction at a heating rate of 1°C / min in a temperature range of +23 to +80°C (CLTE 23-80°C, MD) of less than 95 μm / m°C, preferably 70 to 90 μm / m°C and / or a coefficient of linear thermal expansion in the transverse direction at a heating rate of 1°C / min in a temperature range of +23 to +80°C (CLTE 23-80°C, MD) of less than 145 μm / m°C, preferably 110 to 140 μm / m°C. The invention relates to a thermal expansion coefficient of the present invention which is preferably less than 100 μm / m°C, preferably 23-80°C, TD), and / or a coefficient of linear thermal expansion in the longitudinal direction at a heating rate of 1°C / min in the temperature range of -30 to +80°C (CLTE-30-80°C, MD) of less than 75 μm / m°C, preferably 50 to 75 μm / m°C, and / or a coefficient of linear thermal expansion in the transverse direction (CLTE-30-80°C, TD) of less than 125 μm / m°C, preferably 100 to 120 μm / m°C in the temperature range of -30 to +80°C at a heating rate of 1°C / min, all of which are measured according to ISO 11359-2:1999.
15. Use of the composition according to any one of claims 1 to 9 for injection molding of articles, preferably automotive articles.
Citation Information
Patent Citations
Optical reading device without an objective
EP0261027A1
A method for the modification of catalysts intended for the polymerization of olefins
EP0491566A2
Coarse grained polyolefin, production thereof and a procatalyst containing a transesterification product between a lower alcohol and dioctylphthalate used therefore
EP0586390A1
A procatalyst for polymerization of olefins containing a trans-esterification product of a lower alcohol and a phthalic acid ester
EP0591224A1
Process and apparatus for preparing propylene homopolymers and copolymers
EP0887379A1